Platinum group metal ion supported catalyst and method for forming carbon-carbon bond

By supporting platinum group metal ions or composite ions in non-particle organic ion exchangers, a platinum group metal ion support catalyst for carbon-carbon bond formation reaction was developed, which solved the problems of insufficient yield of aromatic bromide reactions and difficulty in catalyst recovery in the prior art, and achieved efficient, environmentally friendly and economical carbon-carbon bond formation.

JP7662389B2Active Publication Date: 2025-04-15ORGANO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021068533
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-14
Publication Date
2025-04-15
Estimated Expiration
2041-04-14

AI Technical Summary

Technical Problem

In the prior art, when using a platinum group metal catalyst to carry out the carbon-carbon bond formation reaction in aromatic bromide, the yield is insufficient and the catalyst is difficult to recover, which affects environmental protection and economicality.

Method used

A platinum group metal ion support catalyst was developed to form a catalyst structure with a continuous framework and continuous pores by supporting platinum group metal ions or composite ions in a non-particle organic ion exchanger. The catalyst exhibits high activity in aqueous solvents and can effectively support the carbon-carbon bond formation reaction.

Benefits of technology

The efficient formation of carbon-carbon bonds in aromatic bromides is achieved, which improves yields, and by supporting the design of the catalyst, the recovery of catalysts is simplified and metal pollution is reduced, and environmental protection and economicality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662389000012
    Figure 0007662389000012
  • Figure 0007662389000013
    Figure 0007662389000013
  • Figure 0007662389000014
    Figure 0007662389000014
Patent Text Reader

Abstract

To provide a platinum group metal ion supported catalyst which enables a carbon-carbon bond forming reaction to be performed in high yield even in an aromatic bromide.SOLUTION: Provided is a platinum group metal ion supported catalyst in which at least one of platinum group metal ions and platinum group metal complex ions is supported by an ion exchanger comprising a polymer chain represented by a general formula (1). (In the formula, R1 represents a C4-22 alkyl group which may be substituted or a benzyl group which may be substituted with a C1-6 alkyl group which may be substituted, with a halogen atom, with a C1-6 alkoxy group which may be substituted, with an amino group which may be substituted, with a cyano group, or with a nitro group; R2 and R3 represent each independently a C1-4 alkyl group; L represents a linker site; and Polymer represents a polymer chain).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a platinum group metal ion supported catalyst and a carbon-carbon bond forming method in which a reaction to form a carbon-carbon bond is carried out using the platinum group metal ion supported catalyst. [Background technology]

[0002] Carbon-carbon formation reactions (coupling reactions) catalyzed by platinum group metals such as palladium, such as the Suzuki-Miyaura coupling, Sonogashira coupling, and Mizoroki-Heck coupling, have become increasingly important in recent years in the synthesis processes of pharmaceutical intermediates and highly functional materials such as organic electroluminescence (EL) materials.

[0003] Conventionally, the platinum group metal catalysts have often been used in homogeneous systems and have shown high catalytic activity, but have problems such as the difficulty of recovering the catalyst and the contamination of the product with the metal catalyst. Therefore, heterogeneous catalysts have been developed in which the catalyst is supported on a carrier, making it easier to recover the catalyst and reducing metal contamination of the product, and in recent years, a method has also been developed in which a reaction substrate solution is passed through the heterogeneous catalyst to continuously form carbon-carbon bonds.

[0004] For example, Patent Document 1 reports a method for continuously forming carbon-carbon bonds using a catalyst in which palladium is supported on a porous silica carrier, but does not disclose any actual reaction examples.

[0005] Patent Documents 2 and 3 disclose a method for forming carbon-carbon bonds using a catalyst in which a platinum group metal is supported on the wall surface of a fine channel with a width of 1 mm and a depth of 20 μm. However, for reasons that are unclear, in the disclosed reaction examples, water is not used as a solvent and the flow rate of the reaction substrate solution is only 1 μm / min, which poses problems in terms of environmental impact and production efficiency.

[0006] Non-Patent Document 1 reports a method for continuously forming carbon-carbon bonds in a column packed with a catalyst in which palladium is supported on an organic support. However, complex chemical conversion is required to obtain the organic support, and, for reasons that are unclear, a large amount of diatomaceous earth must be mixed in when using a palladium-supported catalyst.

[0007] On the other hand, the present inventors have developed a catalyst in which a platinum group metal is supported on a non-particulate organic ion exchanger having three-dimensionally continuous pores, and have reported in Patent Documents 4 and 5 that this catalyst exhibits high catalytic activity in an aqueous solvent in a carbon-carbon bond forming reaction.

[0008] According to the methods disclosed in Patent Document 4 and Patent Document 5, a platinum group metal supported catalyst in which a platinum group metal is supported on a non-particulate organic ion exchanger is used as a catalyst, whereby a carbon-carbon bond forming reaction can be carried out in a high yield in an aqueous solvent. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 5638862 [Patent Document 2] Patent No. 5255215 Publication [Patent Document 3] JP 2008-212765 A [Patent Document 4] JP 2014-015420 A [Patent Document 5] JP 2016-190853 A [Non-patent literature]

[0010] [Non-Patent Document 1] ChemCatChem, 2019, Issue 11, Page 2427 Summary of the Invention [Problem to be solved by the invention]

[0011] However, in the reaction examples of Patent Documents 4 and 5, it is shown that the carbon-carbon bond forming reaction can be carried out in high yield only when the aromatic halide raw material is a highly reactive aromatic iodide, but the yield is insufficient when it is an aromatic bromide, and the usable raw materials are limited.

[0012] An object of the present invention is to provide a platinum group metal ion supported catalyst capable of carrying out a carbon-carbon bond forming reaction in high yield even with aromatic bromides, and a carbon-carbon bond forming method using the platinum group metal ion supported catalyst. [Means for solving the problem]

[0013] The present invention relates to 1. A supported platinum group metal ion catalyst for carbon-carbon bond forming reactions comprising: General formula (1) [ka] (R in the formula 1 teeth , charcoal Prime numbers 6 from 20 or an alkyl group of , charcoal From prime number 1 4 Alkyl Based on an optionally substituted benzyl group; R 2 ,R 3 each independently represents an alkyl group having 1 to 4 carbon atoms, L represents a linker moiety, and Polymer represents a polymer chain. At least one of platinum group metal ions and platinum group metal complex ions is supported on an ion exchanger composed of a polymer chain represented by the following formula:

[0014] In the platinum group metal ion-supported catalyst, the ion exchanger is preferably a non-particulate organic porous ion exchanger comprising a continuous framework phase and a continuous pore phase, the thickness of the continuous framework being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, the ion exchange capacity per weight in a dry state being in the range of 1 to 9 mg equivalent / g, and the ion exchange groups being distributed throughout the ion exchanger.

[0015] In the platinum group metal ion-supported catalyst, it is preferred that the non-particulate organic porous ion exchanger has a continuous macropore structure having interconnected macropores and common openings in the walls of the macropores with an average diameter in the range of 1 to 1000 μm, the total pore volume is in the range of 1 to 50 mL / g, the ion exchange capacity per weight in a dry state is in the range of 1 to 9 mg equivalent / g, and ion exchange groups are distributed in the organic porous ion exchanger.

[0016] In the platinum group metal ion-supported catalyst, it is preferred that the non-particulate organic porous ion exchanger is formed by agglomeration of organic polymer particles having an average particle size of 1 to 50 μm to form a three-dimensionally continuous skeleton portion, and has three-dimensionally continuous pores having an average diameter of 20 to 100 μm between the skeletons, has a total pore volume of 1 to 10 mL / g, has an ion exchange capacity per weight in a dry state of 1 to 9 mg equivalent / g, and has ion exchange groups distributed in the organic porous ion exchanger.

[0017] In the platinum group metal ion-supported catalyst, it is preferred that the non-particulate organic porous ion exchanger is a continuous macropore structure in which bubble-like macropores overlap each other and the overlapping portions form openings with an average diameter of 30 to 300 μm, the total pore volume is in the range of 0.5 to 10 mL / g, the ion exchange capacity per weight in a dry state is in the range of 1 to 9 mg equivalent / g, ion exchange groups are distributed in the organic porous ion exchanger, and in an SEM image of a cut surface of the continuous macropore structure, the area of ​​the framework portion appearing on the cross section is in the range of 25 to 50% of the image area.

[0018] In the platinum group metal ion-supported catalyst, it is preferable that the non-particulate organic porous ion exchanger is a bicontinuous structure consisting of a three-dimensionally continuous skeleton having a thickness of 1 to 60 μm and composed of an aromatic vinyl polymer containing crosslinked structural units in the range of 0.1 to 5.0 mol % of all structural units into which ion exchange groups have been introduced, and three-dimensionally continuous pores having an average diameter of 10 to 200 μm between the skeletons, the total pore volume is in the range of 0.5 to 10 mL / g, the ion exchange capacity per weight in a dry state is in the range of 1 to 9 mg equivalent / g, and the ion exchange groups are distributed in the organic porous ion exchanger.

[0019] In the platinum group metal ion-supported catalyst, it is preferred that the non-particulate organic porous ion exchanger comprises a continuous skeleton phase and a continuous pore phase, the skeleton has a plurality of particles having a diameter of 4 to 40 μm adhered to the surface or a plurality of protrusions having a size of 4 to 40 μm formed on the skeleton surface of the organic porous material, the average diameter of the continuous pores is in the range of 10 to 200 μm, the total pore volume is in the range of 0.5 to 10 mL / g, the ion exchange capacity per weight in a dry state is in the range of 1 to 9 mg equivalent / g, and ion exchange groups are distributed in the organic porous ion exchanger.

[0020] In the platinum group metal ion supported catalyst, the amount of at least one of the platinum group metal ions and platinum group metal complex ions supported is preferably in the range of 0.01 to 10.0 mass % calculated as platinum group metal atoms.

[0022] In the platinum group metal ion supported catalyst, R 1 is preferably a dodecyl group or a benzyl group.

[0023] In the platinum group metal ion supported catalyst, R 2 ,R 3 is preferably each independently a methyl group or an ethyl group.

[0024] In the platinum group metal ion supported catalyst, R 2 ,R 3 is preferably a methyl group.

[0025] In the above platinum group metal ion supported catalyst, L in general formula (1) is preferably a methylene group.

[0026] In the platinum group metal ion supported catalyst, the polymer chain of the ion exchanger is preferably a styrene-divinylbenzene copolymer.

[0027] The present invention relates to a method for forming a carbon-carbon bond by (1) reacting an aromatic halide with an organoboron compound, (2) reacting an aromatic halide with a compound having an alkynyl group at a terminal, or (3) reacting an aromatic halide with a compound having an alkenyl group to form a carbon-carbon bond, the method comprising: introducing a raw material liquid (i) containing an aromatic halide and the organoboron compound, a raw material liquid (ii) containing an aromatic halide and the compound having an alkynyl group at a terminal, or a raw material liquid (iii) containing an aromatic halide and the compound having an alkenyl group into a vessel filled with a platinum group metal ion supported catalyst through an inlet path of the vessel; passing the raw material liquid through the platinum group metal ion supported catalyst; and discharging the reaction liquid through a discharge path of the vessel to carry out a carbon-carbon bond forming reaction, and the platinum group metal ion supported catalyst is The above A method for carbon-carbon bond formation using platinum group metal ion supported catalysts.

[0028] In the carbon-carbon bond forming method, the carbon-carbon bond forming reaction is preferably carried out in the presence of an inorganic base.

[0029] In the carbon-carbon bond forming method, it is preferable that the raw material liquid (i), the raw material liquid (ii), or the raw material liquid (iii) is an inorganic base-dissolved raw material liquid in which a raw material and an inorganic base are dissolved in water or a hydrophilic solvent, and the inorganic base-dissolved raw material liquid is introduced into the filled vessel through an inlet path of the filled vessel in which the platinum group metal ion-supported catalyst is filled, the inorganic base-dissolved raw material liquid is passed through the platinum group metal ion-supported catalyst, and the reaction liquid is discharged from a discharge path of the filled vessel, thereby carrying out a carbon-carbon bond forming reaction.

[0030] In the carbon-carbon bond forming method, it is preferable that the raw material liquid (i), the raw material liquid (ii), or the raw material liquid (iii) is a hydrophobic solvent raw material liquid in which a raw material is dissolved in a hydrophobic organic solvent, and a mixture of the hydrophobic solvent raw material liquid and an inorganic base aqueous solution in which an inorganic base is dissolved is introduced into the filled vessel through an inlet path of the filled vessel in which the platinum group metal ion supported catalyst is filled, the hydrophobic solvent raw material liquid and the inorganic base aqueous solution are passed through the platinum group metal ion supported catalyst, and the reaction liquid is discharged from a discharge path of the filled vessel, thereby carrying out a carbon-carbon bond forming reaction. Effect of the Invention

[0031] According to the present invention, it is possible to provide a platinum group metal ion supported catalyst capable of carrying out a carbon-carbon bond forming reaction in high yield even in aromatic bromides, and a carbon-carbon bond forming method using the platinum group metal ion supported catalyst. [Brief description of the drawings]

[0032] [Figure 1] 1 is a SEM photograph of a first monolith morphology example. [Diagram 2] 1 is a SEM photograph of a second monolith morphology example. [Diagram 3] 11 is an SEM photograph of a third monolith morphology example. [Figure 4] This is a transfer of the skeleton portion shown as a cross section in the SEM photograph of FIG. [Diagram 5]11 is an SEM photograph of a fourth monolith morphology example. [Figure 6] FIG. 13 is a schematic diagram of the co-continuous structure of the fourth monolith. [Figure 7] 1 is a SEM photograph of an example of the morphology of the monolith intermediate (4). [Figure 8] FIG. 4 is a schematic cross-sectional view of a protrusion. [Figure 9] 5 is a SEM photograph of an example of the monolith shape of No. 5-1. [Figure 10] 1 is a SEM photograph of the monolith intermediate obtained in Example 1. [Figure 11] 1 is a SEM photograph of the monolith obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The following describes an embodiment of the present invention. The embodiment is merely an example of implementing the present invention, and the present invention is not limited to the embodiment.

[0034] <Platinum group metal ion supported catalyst> [Ion exchanger] The platinum group metal ion supported catalyst according to an embodiment of the present invention is represented by the general formula (1) [ka] (R in the formula 1 represents an optionally substituted alkyl group having 4 to 22 carbon atoms; or an optionally substituted alkyl group having 1 to 6 carbon atoms, a halogen atom, an optionally substituted alkoxy group having 1 to 6 carbon atoms, an optionally substituted amino group, a cyano group, or a benzyl group optionally substituted with a nitro group; R 2 ,R 3 each independently represents an alkyl group having 1 to 4 carbon atoms, L represents a linker moiety, and Polymer represents a polymer chain. At least one of platinum group metal ions and platinum group metal complex ions is supported on an ion exchanger composed of a polymer chain represented by the following formula:

[0035] As a result of intensive research, the present inventors have found that a catalyst in which at least one of platinum group metal ions and platinum group metal complex ions is supported on an ion exchanger composed of a polymer chain represented by the above general formula (1), i.e., a catalyst in which a platinum group metal is supported in an ion state on an ion exchanger composed of a polymer chain represented by the above general formula (1), can carry out a carbon-carbon bond forming reaction in high yield even with aromatic bromides. In particular, it has been found that the yield is high even when aromatic bromides are used as raw materials in a fixed-bed continuous flow carbon-carbon bond reaction.

[0036] This is because the ion exchanger composed of the polymer chain represented by the above general formula (1) is R 1 It is considered that the presence of the alkyl group having 4 to 22 carbon atoms or the benzyl group increases lipophilicity, and in a carbon-carbon bonding reaction in a fixed-bed continuous flow system or the like, contact between the organic phase and the aqueous phase is efficiently carried out on the surface of the ion exchanger.

[0037] R in general formula (1) 1 represents an optionally substituted alkyl group having 4 to 22 carbon atoms; or R 1 represents a benzyl group which may be substituted with an optionally substituted alkyl group having 1 to 6 carbon atoms, a benzyl group which may be substituted with a halogen atom, a benzyl group which may be substituted with an optionally substituted alkoxy group having 1 to 6 carbon atoms, a benzyl group which may be substituted with an optionally substituted amino group, a benzyl group which may be substituted with a cyano group, or a benzyl group which may be substituted with a nitro group. The optionally substituted benzyl group is a benzyl group in which the phenyl group of the benzyl group may be substituted with a substituent.

[0038] The alkyl group having 4 to 22 carbon atoms may be linear, branched, or cyclic. From the viewpoints of high reaction yield during production, easy availability of raw materials, and good performance, an alkyl group having 6 to 20 carbon atoms is preferred, and an alkyl group having 6 to 18 carbon atoms is more preferred.

[0039] The alkyl group having 1 to 6 carbon atoms, which may be substituted with a benzyl group, may be linear, branched, or cyclic. From the viewpoints of easy availability of raw materials and good performance, an alkyl group having 1 to 4 carbon atoms is preferred, and a methyl group or an ethyl group is more preferred.

[0040] Examples of the halogen atom which may be substituted on the benzyl group include a chlorine atom, a bromine atom, and an iodine atom. A chlorine atom is preferred from the viewpoints of low cost production of raw materials and easy availability of raw materials.

[0041] The alkoxy group having 1 to 6 carbon atoms which may be substituted with a benzyl group may be linear, branched or cyclic. In terms of easy availability of raw materials and good performance, an alkoxy group having 1 to 4 carbon atoms is preferred, and a methoxy group or an ethoxy group is more preferred.

[0042] Examples of the substituent that may be "optionally substituted" with the alkyl group having 4 to 22 carbon atoms, the alkyl group having 1 to 6 carbon atoms, or the alkoxy group having 1 to 6 carbon atoms include a nitro group, a cyano group, and a halogen atom.

[0043] In the case where the amino group is "optionally substituted", examples of the substituent include an alkyl group having 1 to 8 carbon atoms, a phenyl group, a fluoroalkyl group having 1 to 4 carbon atoms, and the like.

[0044] The alkyl group having 1 to 8 carbon atoms which may be substituted by the amino group may be linear, branched or cyclic. From the viewpoint of high reaction yield during production, etc., an alkyl group having 1 to 4 carbon atoms is preferred, and a methyl group or an ethyl group is more preferred.

[0045] The fluoroalkyl group having 1 to 4 carbon atoms which may be substituted with an amino group may be linear, branched or cyclic. From the viewpoint of easy availability of raw materials, etc., a fluoroalkyl group having 1 to 2 carbon atoms is preferred, and a trifluoromethyl group or a 2,2,2-trifluoroethyl group is more preferred.

[0046] R in general formula (1) 1 is preferably an alkyl group having 6 to 20 carbon atoms or a benzyl group which may be substituted with an alkyl group having 1 to 4 carbon atoms, and more preferably a dodecyl group or a benzyl group.

[0047] R in general formula (1) 2 ,R 3 each independently represents an alkyl group having 1 to 4 carbon atoms. The alkyl group having 1 to 4 carbon atoms may be linear, branched, or cyclic. As the alkyl group having 1 to 4 carbon atoms, a methyl group or an ethyl group is preferred from the viewpoint of high reaction yield during production, and a methyl group is more preferred.

[0048] L in general formula (1) represents a linker moiety. Examples of the linker moiety include an alkylene group having 1 to 4 carbon atoms which may be substituted with an oxy group, and from the viewpoint of high reaction yield during production, a methylene group, an ethylene group, or a 1-oxyethylene group is preferred, and a methylene group is more preferred.

[0049] Polymer in the general formula (1) represents a polymer chain. Examples of the polymer chain include aromatic vinyl polymers such as polystyrene, poly(α-methylstyrene), and polyvinylbenzyl chloride; polyolefins such as polyethylene and polypropylene; poly(halogenated polyolefins) such as polyvinyl chloride and polytetrafluoroethylene; nitrile polymers such as polyacrylonitrile; and (meth)acrylic polymers such as polymethacrylic acid esters and polyacrylic acid esters. The polymer chain may be a polymer obtained by copolymerizing a single vinyl monomer and a crosslinking agent, or a polymer obtained by polymerizing multiple vinyl monomers and a crosslinking agent, or may be a blend of two or more polymers. Among these, crosslinked polymers of aromatic vinyl polymers are preferred in terms of ease of forming a continuous structure, ease of introducing ion exchange groups, high mechanical strength, and high stability against acids or alkalis, and in particular, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred, with styrene-divinylbenzene copolymers being more preferred.

[0050] The ion exchanger according to this embodiment may be a particulate ion exchanger or a non-particulate ion exchanger, and is preferably a non-particulate organic porous ion exchanger because the frequency of contact with the raw material liquid increases in the carbon-carbon bond formation method.

[0051] [Non-particulate organic porous ion exchangers] A non-particulate organic porous ion exchanger is a monolithic organic porous body having a continuous skeleton phase and a continuous pore phase, into which an ion exchange group has been introduced. A non-particulate organic porous ion exchanger composed of a polymer chain represented by the above general formula (1) is a basic monolithic organic porous anion exchanger. A monolithic organic porous body has a large number of communicating holes that serve as flow paths between the skeletons. In this specification, the "monolithic organic porous body" is also referred to simply as "monolith", the "monolithic organic porous ion exchanger" is also referred to simply as "monolith ion exchanger", and the "monolithic organic porous intermediate", which is an intermediate (precursor) in the production of a monolith, is also referred to simply as "monolith intermediate".

[0052] The structure of this non-particulate organic porous ion exchanger is disclosed in JP-A-2002-306976, JP-A-2009-007550, JP-A-2009-062512, JP-A-2009-067982, and JP-A-2009-108294.

[0053] The non-particulate organic porous ion exchanger preferably comprises a continuous framework phase and a continuous pore phase, the thickness of the continuous framework being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, the ion exchange capacity per weight in a dry state being in the range of 1 to 9 mg equivalent / g, and the ion exchange groups being distributed in the organic porous ion exchanger. The continuous framework phase and the continuous pore phase are observed by SEM images.

[0054] The thickness of the continuous skeleton of the non-particulate organic porous ion exchanger in a dry state is preferably in the range of 1 to 100 μm. The thickness of the continuous skeleton of the non-particulate organic porous ion exchanger in a dry state is determined by SEM observation. If the thickness of this continuous skeleton is less than 1 μm, the ion exchange capacity per volume may decrease, or the mechanical strength may decrease, so that the non-particulate organic porous ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through it, especially when the liquid is passed through at a high flow rate. If the thickness of this continuous skeleton exceeds 100 μm, the skeleton may become too thick, and the pressure loss during the passage of the raw material liquid may become large.

[0055] The average diameter of the continuous pores of the non-particulate organic porous ion exchanger in a dry state is preferably in the range of 1 to 1000 μm. The average diameter of the continuous pores of the non-particulate organic porous ion exchanger in a dry state is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. If the average diameter of the continuous pores is less than 1 μm, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large. If the average diameter of the continuous pores is more than 1000 μm, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the contact between the reaction liquid and the monolith ion exchanger may be insufficient, resulting in a decrease in catalytic activity.

[0056] The total pore volume of the non-particulate organic porous ion exchanger in a dry state is preferably in the range of 0.5 to 50 mL / g. The total pore volume of the non-particulate organic porous ion exchanger in a dry state is measured by mercury intrusion porosimetry. If the total pore volume is less than 0.5 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may be large. If the total pore volume exceeds 50 mL / g, the mechanical strength of the non-particulate organic porous ion exchanger is reduced, and when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the monolith ion exchanger may be deformed, and the pressure loss during the passage of the liquid may increase, especially when the liquid is passed through at a high flow rate.

[0057] The ion exchange capacity per unit weight of the non-particulate organic porous ion exchanger in a dry state is preferably in the range of 1 to 9 mg equivalent / g. The ion exchange capacity per unit weight of the non-particulate organic porous ion exchanger in a dry state is measured by a method such as neutralization titration or precipitation titration. If the ion exchange capacity is less than 1 mg equivalent / g, the amount of platinum group metal ions or platinum group metal complex ions that can be supported may be reduced. If the ion exchange capacity exceeds 9 mg equivalent / g, the ion exchange group introduction reaction may be carried out under severe conditions, and the oxidation deterioration of the monolith may progress significantly.

[0058] In the non-particulate organic porous ion exchanger, the introduced ion exchange groups are preferably distributed not only on the surface of the monolith but also inside the skeleton of the monolith, i.e., in the organic porous ion exchanger, and more preferably distributed uniformly. "Ion exchange groups are uniformly distributed in the organic porous ion exchanger" means that the ion exchange groups are distributed on the surface and inside the skeleton of the organic porous ion exchanger at least on the order of μm. The distribution of the ion exchange groups is confirmed by using an electron probe microanalyzer (EPMA). If the ion exchange groups are distributed not only on the surface of the monolith but also inside the skeleton of the monolith, the physical and chemical properties of the surface and inside of the monolith can be made almost uniform, improving the durability against swelling and shrinkage.

[0059] In the non-particulate organic porous ion exchanger, the material constituting the continuous skeleton is an organic polymer material having a crosslinked structure, which is the Polymer portion in the above general formula (1). The polymer material preferably contains 0.1 to 30 mol % of crosslinked structural units, more preferably 0.1 to 20 mol % of crosslinked structural units, based on the total structural units constituting the polymer material.

[0060] [First to fifth monolithic ion exchangers] More specific embodiments of the non-particulate organic porous ion exchanger include, for example, the following first monolithic organic porous ion exchanger (monolith ion exchanger) to fifth monolithic organic porous ion exchanger (monolith ion exchanger). In the following description, the description of the same configuration as the above non-particulate organic porous ion exchanger is omitted.

[0061] (First monolith ion exchanger) The first monolith ion exchanger has a continuous macropore structure with interconnected macropores and common openings (mesopores) with an average diameter of 1 to 1000 μm in the walls of the macropores, a total pore volume in the range of 1 to 50 mL / g, an ion exchange capacity per weight in a dry state in the range of 1 to 9 mg equivalent / g, and ion exchange groups distributed in the organic porous ion exchanger.

[0062] The first monolith ion exchanger is a continuous macropore structure having continuous macropores (fine pores) as shown in Fig. 1. The first monolith ion exchanger and a method for producing it are disclosed in JP-A-2002-306976.

[0063] The first monolith ion exchanger has macropores that are connected to each other and common openings (mesopores) located in the walls of the macropores. The mesopores have overlapping portions where the macropores overlap each other. The overlapping portions of the mesopores preferably have an average diameter in the dry state of 1 to 1000 μm, more preferably in the range of 10 to 200 μm, and even more preferably in the range of 20 to 200 μm. The average diameter of the openings of the first monolith in the dry state is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry.

[0064] Most of such first monolith ion exchangers have an open pore structure in which the voids formed by the macropores and mesopores serve as flow paths. If the average diameter of the overlapping parts of the mesopores in a dry state is less than 1 μm, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become significantly large. If the average diameter of the overlapping parts of the mesopores in a dry state exceeds 1000 μm, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the contact between the reaction liquid and the monolith ion exchanger may be insufficient, resulting in a decrease in catalytic activity. The number of overlapping macropores is, for example, 1 to 12 in one macropore, and in most cases, 3 to 10. Since the first monolith ion exchanger has the continuous macropore structure described above, groups of macropores and groups of common pores can be formed almost uniformly, and the pore volume and specific surface area can be made significantly larger than those of particle agglomeration type porous bodies such as those described in JP-A-8-252579, etc.

[0065] The total pore volume per weight of the first monolith ion exchanger in a dry state is preferably in the range of 1 to 50 mL / g, more preferably in the range of 2 to 30 mL / g. If the total pore volume per weight in a dry state is less than 1 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and further, the permeation amount per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume per weight in a dry state exceeds 50 mL / g, the mechanical strength decreases, and the monolith ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, particularly at a high flow rate.

[0066] The ion exchange capacity per weight in a dry state is as described above. In addition, the fact that "the ion exchange groups are distributed in the organic porous ion exchanger" is as described above.

[0067] (First method for producing monolithic ion exchanger) The first monolith ion exchanger can be produced, for example, by the following method.

[0068] For example, an oil-soluble monomer not containing an ion exchange group, a surfactant, water, and optionally a polymerization initiator can be mixed to obtain a water-in-oil emulsion, which can then be polymerized to form a first monolith.

[0069] The oil-soluble monomer not containing an ion exchange group used in the production of the first monolith refers to a monomer that does not contain an ion exchange group, has low solubility in water, and is lipophilic. Examples of this monomer include styrene, α-methylstyrene, vinylbenzyl chloride, ethylene, propylene, vinyl chloride, vinyl bromide, acrylonitrile, methacrylonitrile, vinyl acetate, methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, butanediol diacrylate, methyl methacrylate, ethyl methacrylate, 2-ethylhexyl methacrylate, and ethylene glycol dimethacrylate. These monomers can be used alone or in combination of two or more. However, it is preferable to select a crosslinkable monomer such as divinylbenzene or ethylene glycol dimethacrylate as at least one component of the oil-soluble monomer, and set the content thereof in the range of, for example, 0.3 to 10 mol%, preferably 0.3 to 5 mol%, in the total oil-soluble monomer, in order to quantitatively introduce ion exchange groups in the subsequent process and ensure sufficient mechanical strength for practical use.

[0070] The surfactant used in the production of the first monolith is not particularly limited as long as it can form a water-in-oil (W / O) emulsion when an oil-soluble monomer not containing an ion exchange group is mixed with water. Examples of the surfactant include nonionic surfactants such as sorbitan monooleate, sorbitan monolaurate, and polyoxyethylene nonylphenyl ether; anionic surfactants such as potassium oleate, sodium dodecylbenzenesulfonate, and dioctyl sodium sulfosuccinate; cationic surfactants such as distearyl dimethyl ammonium chloride; and amphoteric surfactants such as lauryl dimethyl betaine. These surfactants can be used alone or in combination of two or more. A water-in-oil emulsion is an emulsion in which the oil phase is the continuous phase and water droplets are dispersed therein. The amount of surfactant added may be, for example, in the range of about 2 to 70% of the total amount of the oil-soluble monomer and the surfactant. In order to control the shape and size of the cells in the monolith, alcohols such as methanol and stearyl alcohol; carboxylic acids such as stearic acid; hydrocarbons such as octane, dodecane, and toluene; cyclic ethers such as tetrahydrofuran and dioxane, etc. can also be made to coexist in the system.

[0071] In the manufacture of the first monolith, when forming a monolith by polymerization, the polymerization initiator used as necessary is preferably a compound that generates radicals by heat and light irradiation. The polymerization initiator may be water-soluble or oil-soluble, for example, azobisisobutyronitrile, azobisdimethylvaleronitrile, azobiscyclohexanenitrile, azobiscyclohexanecarbonitrile, benzoyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, tetramethylthiuram disulfide, etc. However, in some cases, there are systems in which polymerization proceeds only by heating or light irradiation without adding a polymerization initiator, so in such systems, it is not necessary to add a polymerization initiator.

[0072] In the production of the first monolith, various polymerization conditions for polymerizing the water-in-oil emulsion can be selected depending on the type of monomer, initiator system, etc. When azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, etc. are used as the polymerization initiator, for example, in a sealed container under an inert atmosphere, for example, at 30 to 100°C for 1 to 48 hours, the polymerization can be performed, for example, in a sealed container under an inert atmosphere, at 0 to 30°C for 1 to 48 hours. After the polymerization is completed, the contents are taken out and subjected to Soxhlet extraction with a solvent such as isopropanol to remove unreacted monomers and residual surfactants, to obtain the first monolith.

[0073] Methods for introducing ion exchange groups into the first monolith include, for example, the following methods (1) and (2). (1) Instead of a monomer that does not contain an ion exchange group, a monomer that contains an ion exchange group, for example, the oil-soluble monomer that does not contain an ion exchange group, is polymerized with a monomer to which an ion exchange group has been introduced, to produce a monolith ion exchanger in one step. (2) A monomer that does not contain an ion exchange group is polymerized to form the first monolith, and then an ion exchange group is introduced.

[0074] As a method for introducing an ion exchange group into the first monolith, known methods such as polymer reaction and graft polymerization can be used. As a method for introducing a strongly basic anion exchange group (quaternary ammonium group), for example, there are the following methods (1) to (3). In the method (1), if the monolith is a styrene-divinylbenzene copolymer, etc., a chloromethyl group can be introduced by chloromethyl methyl ether or the like, and then reacted with a desired tertiary amine to introduce the group. In the method (2), the monolith is produced by copolymerizing chloromethylstyrene and divinylbenzene, and then reacted with a desired tertiary amine to introduce the group. In the method (3), a radical initiator group or a chain transfer group can be introduced into the monolith, graft polymerized with glycidyl methacrylate, and then reacted with a desired tertiary amine to introduce the group.

[0075] For example, general formula (2) [ka] (In the formula, L represents a linker moiety, Polymer represents a polymer chain, and X represents a halogen atom, an optionally substituted alkylsulfonyl group having 1 to 8 carbon atoms, or an optionally substituted benzenesulfonyl group.) and a polymer chain represented by General formula (3) [ka] (R in the formula 1 represents an optionally substituted alkyl group having 4 to 22 carbon atoms; or an optionally substituted alkyl group having 1 to 6 carbon atoms, a halogen atom, an optionally substituted alkoxy group having 1 to 6 carbon atoms, an optionally substituted amino group, a cyano group, or a benzyl group optionally substituted with a nitro group; R 2 ,R 3 each independently represents an alkyl group having 1 to 4 carbon atoms. and a tertiary amine represented by the formula: The first monolithic ion exchanger can be produced by reacting

[0076] In the method for producing the ion exchanger, the definitions of L and Polymer in the general formula (2), R 1 ,R 2 ,R 3 The definitions of L, Polymer, and R in general formula (1) are as follows: 1 ,R 2 ,R 3 are the same as the definitions of

[0077] In the general formula (2), X represents a halogen atom, an optionally substituted alkylsulfonyl group having 1 to 8 carbon atoms, or an optionally substituted benzenesulfonyl group.

[0078] Examples of the halogen atom for X include a chlorine atom, a bromine atom, and an iodine atom. A chlorine atom is preferred from the viewpoint of inexpensive production raw materials.

[0079] The alkyl group in the alkylsulfonyl group having 1 to 8 carbon atoms may be linear, branched, or cyclic. A methylsulfonyl group or an ethylsulfonyl group is preferred from the viewpoints of easy availability of raw materials and high reaction yield during production.

[0080] The alkylsulfonyl group having 1 to 8 carbon atoms may be substituted with a cyano group, a nitro group, a halogen atom or the like. From the viewpoint of high reaction yield and the like, a halogen atom is preferred, and a fluorine atom is more preferred.

[0081] The benzenesulfonyl group may be substituted with an alkyl group having 1 to 4 carbon atoms, a nitro group, a cyano group, a halogen atom, or the like, and a methyl group is preferred from the viewpoint of easy availability of raw materials, etc.

[0082] The reaction between the polymer chain represented by general formula (2) and the tertiary amine represented by general formula (3) is carried out by mixing them in an organic solvent such as tetrahydrofuran, DMF, toluene, etc., and heating for 4 to 60 hours at a temperature of, for example, 20 to 130° C. After the reaction, the mixture may be washed with an organic solvent such as methanol or tetrahydrofuran, water, etc.

[0083] (Second monolith ion exchanger) The second monolith ion exchanger is a monolith ion exchanger in which organic polymer particles having an average particle size of 1 to 50 μm are aggregated to form a three-dimensionally continuous skeleton, the skeleton having three-dimensionally continuous pores having an average diameter of 20 to 100 μm between the skeletons, a total pore volume in the range of 1 to 10 mL / g, an ion exchange capacity per weight in a dry state in the range of 1 to 9 mg equivalent / g, and ion exchange groups distributed in the organic porous ion exchanger.

[0084] The second monolith ion exchanger is a particle aggregate type structure formed by aggregating particles, as shown in Fig. 2. The second monolith ion exchanger and a method for producing the same are disclosed in JP 2009-007550 A.

[0085] The second monolith ion exchanger has a three-dimensionally continuous skeleton portion formed by aggregation of organic polymer particles having a crosslinked structural unit and an average particle diameter in a dry state of preferably 1 to 50 μm, more preferably 1 to 30 μm. The second monolith ion exchanger has three-dimensionally continuous pores (continuous pores) between the continuous skeletons, the average diameter in a dry state of preferably 20 to 100 μm, more preferably 20 to 90 μm. An SEM photograph is taken of an arbitrarily extracted portion of the cross section of the second monolith ion exchanger in a dry state, the diameters of the organic polymer particles of all the particles in the SEM photograph are measured, and the average value of these is taken as the average particle diameter. The average diameter of the continuous pores in a dry state is determined by mercury intrusion porosimetry, as in the case of the first monolith ion exchanger.

[0086] If the average particle diameter of the organic polymer particles is less than 1 μm in a dry state, the average diameter of the continuous pores between the skeletons may be as small as less than 20 μm in a dry state. If the average particle diameter of the organic polymer particles exceeds 50 μm, the pressure loss may be large when the platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column. If the average diameter of the continuous pores is less than 20 μm in a dry state, the pressure loss may be large when the platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column. If the average diameter of the continuous pores is more than 100 μm in a dry state, the contact between the reaction liquid and the monolith ion exchanger may be insufficient when the platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column.

[0087] The total pore volume per weight of the second monolith ion exchanger in a dry state is preferably in the range of 1 to 10 mL / g. If the total pore volume is less than 1 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and further, the permeation amount per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume exceeds 10 mL / g, the mechanical strength decreases, and the monolith ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, particularly when the liquid is passed through at a high flow rate.

[0088] The ion exchange capacity per weight in a dry state is as described above. In addition, the fact that "the ion exchange groups are distributed in the organic porous ion exchanger" is as described above.

[0089] (Second method for producing monolithic ion exchanger) The second monolithic ion exchanger can be produced, for example, by the following method.

[0090] For example, a vinyl monomer, a specific amount of a cross-linking agent, an organic solvent and a polymerization initiator can be mixed and polymerized in a static state to obtain a second monolith.

[0091] The vinyl monomer used in the preparation of the second monolith is similar to the monomer used in the preparation of the first monolith.

[0092] The crosslinking agent used in the production of the second monolith preferably contains at least two polymerizable vinyl groups in the molecule and is highly soluble in an organic solvent. Examples of the crosslinking agent include divinylbenzene, divinylbiphenyl, and ethylene glycol dimethacrylate. These crosslinking agents can be used alone or in combination of two or more. Preferred crosslinking agents are aromatic polyvinyl compounds such as divinylbenzene, divinylnaphthalene, and divinylbiphenyl, from the viewpoints of high mechanical strength and stability against hydrolysis. The amount of the crosslinking agent used relative to the total amount of the vinyl monomer and the crosslinking agent ({crosslinking agent / (vinyl monomer+crosslinking agent)}×100) is, for example, in the range of 1 to 5 mol%, preferably in the range of 1 to 4 mol%.

[0093] The organic solvent used in the production of the second monolith is an organic solvent in which the vinyl monomer and the crosslinking agent dissolve but the polymer produced by polymerization of the vinyl monomer hardly dissolves, in other words, it is a poor solvent for the polymer produced by polymerization of the vinyl monomer. For example, when the vinyl monomer is styrene, this organic solvent is an alcohol such as methanol, butanol, octanol, etc.; a chain ether such as diethyl ether, ethylene glycol dimethyl ether, etc.; a chain saturated hydrocarbon such as hexane, octane, decane, etc.

[0094] The polymerization initiator used in the production of the second monolith is preferably a compound that generates radicals by heat and light irradiation. The polymerization initiator is preferably oil-soluble. Examples of the polymerization initiator include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyric acid dimethyl, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, tetramethylthiuram disulfide, and the like. The amount of polymerization initiator used relative to the total amount of vinyl monomer and crosslinking agent ({polymerization initiator / (vinyl monomer+crosslinking agent)}×100) is, for example, in the range of about 0.01 to 5 mol %.

[0095] In the production of the second monolith, when, for example, 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, or the like is used as the polymerization initiator, the polymerization can be carried out, for example, by heating in a sealed container under an inert atmosphere at, for example, 30 to 100°C for 1 to 48 hours. After the polymerization is completed, the contents are taken out, and the second monolith can be obtained by extraction with a solvent such as acetone in order to remove unreacted vinyl monomer and organic solvent.

[0096] In the production of the second monolith, organic polymer particles having an average particle size of 1 to 50 μm can be aggregated by adjusting the polymerization conditions, such as increasing the amount of crosslinking agent, increasing the monomer concentration, and increasing the temperature. By setting the amount of crosslinking agent used relative to the total amount of vinyl monomer and crosslinking agent to a specific amount, three-dimensionally continuous pores having an average diameter of 20 to 100 μm can be formed between the skeletons. By polymerizing under conditions in which the amount of organic solvent used relative to the total amount of organic solvent, monomer, and crosslinking agent used ({organic solvent / (organic solvent+monomer+crosslinking agent)}×100) is, for example, in the range of 30 to 80% by weight, preferably in the range of 40 to 70% by weight, the total pore volume of the monolith can be set to 1 to 5 mL / g.

[0097] The method for introducing ion exchange groups into the second monolith is similar to the method for introducing ion exchange groups into the first monolith.

[0098] (Third monolith ion exchanger) The third monolith ion exchanger is a monolith ion exchanger having a continuous macropore structure in which bubble-like macropores overlap each other and the overlapping portions form openings with an average diameter of 30 to 300 μm, a total pore volume in the range of 0.5 to 10 mL / g, an ion exchange capacity per weight in a dry state in the range of 1 to 9 mg equivalent / g, ion exchange groups distributed in the organic porous ion exchanger, and in an SEM image of a cut surface of the continuous macropore structure, the area of ​​the framework appearing on the cross section is in the range of 25 to 50% of the image area.

[0099] The third monolith ion exchanger has a continuous macropore structure similar to the first monolith ion exchanger, as shown in Fig. 3. The third monolith ion exchanger and a method for producing the same are disclosed in JP 2009-062512 A.

[0100] The continuous pores have overlapping portions where macropores overlap each other. The overlapping portions preferably have an average diameter in the dry state of 30 to 300 μm, more preferably 30 to 200 μm, and even more preferably 40 to 100 μm. This average diameter is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. If the average diameter of the openings in the dry state is less than 30 μm, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and if it exceeds 300 μm, the contact between the reaction liquid and the monolith ion exchanger may be insufficient.

[0101] In the third monolith ion exchanger, in an SEM image of a cut surface of the continuous macropore structure in a dry state, the area of ​​the skeleton portion appearing in the cross section is, for example, in the range of 25 to 50% of the image area, and preferably in the range of 25 to 45%. If the area of ​​the skeleton portion appearing in the cross section is less than 25% of the image area, the skeleton becomes thin, and the mechanical strength decreases, so that when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the monolith ion exchanger may be deformed, particularly when the reaction liquid is passed through the column at a high flow rate. If the area of ​​the skeleton portion appearing in the cross section exceeds 50% of the image area, the skeleton becomes too thick, and when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may increase.

[0102] The conditions for obtaining an SEM image may be such that the skeleton part appearing on the cross section of the cut surface is clearly visible, for example, a magnification of 100 to 600 and a photographic area of ​​about 150 mm x 100 mm. SEM observation is preferably performed using three or more images of different cut locations or photographed locations taken at any location on any cut surface of the third monolith ion exchanger, eliminating subjectivity. The third monolith ion exchanger to be cut is in a dry state. The skeleton part of the cut surface in the SEM image will be described with reference to Figs. 3 and 4. In Figs. 3 and 4, the part that is roughly irregular and appears on the cross section is the "skeleton part appearing on the cross section (reference number 12)", the circular pores appearing in Fig. 3 are openings (mesopores), and those with a relatively large curvature or curved surface are macropores (reference number 13 in Fig. 4). The area of ​​the skeleton part appearing on the cross section in Fig. 4 is 28% of the rectangular image area 11.

[0103] In an SEM image, the area of ​​the skeleton appearing in the cross section of the cut surface can be measured by specifying the skeleton through known computer processing, etc., and then calculating it automatically using a computer, etc., or manually. As a manual calculation, there can be mentioned a method of replacing an indefinite shape object with an aggregate of a square, triangle, circle, trapezoid, etc., and stacking them to determine the area.

[0104] The total pore volume per weight of the third monolith ion exchanger in a dry state is preferably in the range of 0.5 to 10 mL / g, more preferably in the range of 0.8 to 8 mL / g. If the total pore volume is less than 0.5 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and further, the amount of permeated fluid per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume exceeds 10 mL / g, the mechanical strength decreases, and the monolith ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, particularly when the liquid is passed through at a high flow rate. Furthermore, the contact efficiency between the reaction liquid and the monolith ion exchanger may decrease.

[0105] The ion exchange capacity per weight in a dry state is as described above. In addition, the fact that "the ion exchange groups are distributed in the organic porous ion exchanger" is as described above.

[0106] (Third method for producing monolithic ion exchanger) The third monolith ion exchanger can be produced, for example, by the following method.

[0107] For example, a water-in-oil emulsion is prepared by stirring a mixture of an oil-soluble monomer not containing an ion exchange group, a surfactant, and water. Then, the following steps I, II, and III are carried out to obtain a third monolith. In step I, the water-in-oil emulsion is polymerized to obtain a monolithic organic porous intermediate (hereinafter also referred to as monolith intermediate (3)) having a continuous macropore structure with a total pore volume in the range of 5 to 16 mL / g. In step II, a mixture containing a vinyl monomer, a crosslinking agent having at least two or more vinyl groups in one molecule, an organic solvent in which the vinyl monomer and the crosslinking agent are dissolved but the polymer produced by polymerization of the vinyl monomer is not dissolved, and a polymerization initiator is prepared. In step III, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (3) obtained in step I to obtain a third monolith having a skeleton thicker than that of the monolith intermediate (3).

[0108] Step I is the same as in the first method for producing a monolithic ion exchanger.

[0109] The monolith intermediate (3) obtained in step I has a continuous macropore structure. When this is present in a polymerization system, a porous structure having a sturdy skeleton can be formed using the structure of the monolith intermediate (3) as a model. The crosslink density of the polymer material is preferably in the range of, for example, 0.3 to 10 mol %, and more preferably 0.3 to 5 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material of the monolith intermediate (3).

[0110] The total pore volume per weight in a dry state of the monolith intermediate (3) obtained in step I is, for example, in the range of 5 to 16 mL / g, and preferably in the range of 6 to 16 mL / g. In order to set the total pore volume of the monolith intermediate (3) in the above numerical range, the ratio of monomer to water may be, for example, in the range of about 1:5 to 1:20.

[0111] The monolith intermediate (3) obtained in step I has an average diameter of openings (mesopores) which are overlapping portions of macropores, in the range of, for example, 20 to 200 μm in a dry state.

[0112] Step II is a step of preparing a mixture containing a vinyl monomer, a crosslinking agent having at least two vinyl groups in one molecule, an organic solvent that dissolves the vinyl monomer and the crosslinking agent but not the polymer produced by polymerization of the vinyl monomer, and a polymerization initiator. Note that the order of steps I and II may be any.

[0113] The vinyl monomer used in step II may be any lipophilic vinyl monomer that contains a polymerizable vinyl group in the molecule and has high solubility in an organic solvent, and it is preferable to select a vinyl monomer that produces the same or similar polymer material as the monolith intermediate (3) that is coexisted in the polymerization system. Specific examples of these vinyl monomers are the same as those used in the production of the first monolith.

[0114] The amount of the vinyl monomer used in step II is, for example, in the range of 3 to 50 times, and preferably in the range of 4 to 40 times, by weight, the amount of the monolith intermediate (3) that is allowed to coexist during polymerization.

[0115] The cross-linking agent used in step II is the same as the cross-linking agent used in the preparation of the second monolith.

[0116] The organic solvent used in step II is the same as that used in the production of the second monolith. The amount of the organic solvent used is preferably such that the concentration of the vinyl monomer is, for example, 30 to 80% by weight.

[0117] The polymerization initiator used in step II is the same as the polymerization initiator used in the production of the second monolith.

[0118] In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (3) obtained in step I, to obtain a third monolith having a skeleton thicker than that of the monolith intermediate (3). When the monolith intermediate (3) having a continuous macropore structure is present in the above polymerization system, a third monolith can be obtained.

[0119] In step III, for example, in a reaction vessel, the monolith intermediate (3) is placed in a state of being impregnated with the mixture (solution). The mixture obtained in step II and the monolith intermediate (3) may be mixed in a ratio, for example, such that the amount of vinyl monomer added is in the range of 3 to 50 times, preferably 4 to 40 times, by weight, relative to the monolith intermediate (3). In the reaction vessel, the vinyl monomer and crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate, and polymerization proceeds within the skeleton of the monolith intermediate (3).

[0120] In the III step, various polymerization conditions are selected depending on the type of monomer, the type of polymerization initiator, and the like. For example, when 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, or the like is used as the polymerization initiator, the polymerization may be carried out, for example, at 30 to 100°C for 1 to 48 hours in a sealed container under an inert atmosphere. By the thermal polymerization, the vinyl monomer and crosslinking agent adsorbed and distributed in the skeleton of the monolith intermediate (3) are polymerized in the skeleton, and the skeleton can be thickened. After the polymerization is completed, the contents are taken out, and for the purpose of removing the unreacted vinyl monomer and the organic solvent, the third monolith can be obtained by extraction with a solvent such as acetone.

[0121] The third monolith ion exchanger can be obtained, for example, by carrying out step IV in which an ion exchange group is introduced into the third monolith obtained in step III. The method for introducing the ion exchange group into the third monolith is the same as the method for introducing the ion exchange group into the first monolith.

[0122] (Fourth monolith ion exchanger) The fourth monolith ion exchanger is a bicontinuous structure consisting of a three-dimensionally continuous skeleton having a thickness of 1 to 60 μm and composed of an aromatic vinyl polymer containing crosslinked structural units in the range of 0.1 to 5.0 mol % of all structural units having ion exchange groups introduced therein, and three-dimensionally continuous pores having an average diameter of 10 to 200 μm between the skeletons, the total pore volume being in the range of 0.5 to 10 mL / g and the ion exchange capacity per weight in a dry state being in the range of 1 to 9 mg equivalent / g, and the ion exchange groups being distributed in the organic porous ion exchanger.

[0123] As shown in Figs. 5 and 6, the fourth monolith ion exchanger has a continuous skeleton phase 1 (continuous skeleton) and a continuous pore phase 2 (continuous pores), which are intertwined to form a three-dimensionally continuous bicontinuous structure 10. The pore phase 2 has higher continuity and almost no deviation in size compared to the first and second monoliths. The fourth monolith ion exchanger is considered to have high mechanical strength because of its thick skeleton. The fourth monolith ion exchanger and a method for producing the same are disclosed in JP 2009-067982 A.

[0124] The continuous skeleton is composed of a vinyl polymer (such as an aromatic vinyl polymer) containing 0.1 to 5.0 mol % of crosslinked structural units in all structural units to which ion exchange groups have been introduced, and the thickness of the continuous skeleton is three-dimensionally continuous, for example, in the range of 1 to 60 μm, preferably in the range of 3 to 58 μm, in a dry state. If the crosslinked structural units are less than 0.1 mol %, the mechanical strength may be insufficient, and if they exceed 5.0 mol %, the structure of the porous body may easily deviate from the co-continuous structure. If the thickness of the continuous skeleton is less than 1 μm in a dry state, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the monolith ion exchanger may be deformed, especially when the reaction liquid is passed through the column at a high flow rate. If the thickness of the continuous skeleton is more than 60 μm in a dry state, the skeleton becomes too thick, and if a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may increase.

[0125] The continuous pores are three-dimensionally continuous between the continuous skeletons, for example, with an average diameter in the range of 10 to 200 μm, preferably 15 to 180 μm, in a dry state. If the average diameter of the continuous pores is less than 10 μm in a dry state, when a reaction liquid is passed through a column packed with a platinum group metal ion-supported catalyst, the pressure loss during the passage of the liquid may become large. If the average diameter exceeds 200 μm, when a reaction liquid is passed through a column packed with a platinum group metal ion-supported catalyst, the contact between the reaction liquid and the monolith ion exchanger may be insufficient.

[0126] The aforementioned average diameter is measured by mercury intrusion porosimetry and refers to the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry. The thickness of the continuous skeleton in a dry state is determined by SEM observation of the fourth monolith ion exchanger in a dry state. Specifically, SEM observation of the fourth monolith ion exchanger in a dry state is performed at least three times, the thickness of the skeleton in the obtained image is measured, and the average value of these is taken as the thickness of the continuous skeleton. Note that the skeleton is rod-shaped and has a circular cross-sectional shape, but may also include one with a cross-section of different diameters such as an elliptical cross-sectional shape. In this case, the thickness is the average of the minor axis and the major axis.

[0127] The total pore volume per weight of the fourth monolith ion exchanger in a dry state is, for example, in the range of 0.5 to 10 mL / g. If the total pore volume is less than 0.5 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and further, the amount of permeated fluid per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume exceeds 10 mL / g, the mechanical strength decreases, and the monolith ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, particularly when the reaction liquid is passed through the column at a high flow rate. Furthermore, the contact efficiency between the reaction liquid and the monolith ion exchanger may decrease.

[0128] Examples of vinyl polymers (aromatic vinyl polymers) constituting the continuous backbone include polystyrene, poly(α-methylstyrene), polyvinylbenzyl chloride, etc. The above polymer may be a polymer obtained by copolymerizing a single vinyl monomer and a crosslinking agent, a polymer obtained by polymerizing a plurality of vinyl monomers and a crosslinking agent, or a blend of two or more polymers. Among these organic polymer materials, styrene-divinylbenzene copolymers and vinylbenzyl chloride-divinylbenzene copolymers are preferred because of the ease of forming a co-continuous structure, the ease of introducing ion exchange groups, high mechanical strength, and high stability against acids or alkalis.

[0129] The ion exchange capacity per weight in a dry state is as described above. In addition, the fact that "the ion exchange groups are distributed in the organic porous ion exchanger" is as described above.

[0130] (Fourth method for producing monolithic ion exchanger) The fourth monolithic ion exchanger can be produced, for example, by the following method.

[0131] For example, the fourth monolith can be obtained by preparing a water-in-oil emulsion and then carrying out the following steps I to III. In step I, for example, the water-in-oil emulsion can be polymerized to obtain a monolithic organic porous intermediate (hereinafter, monolith intermediate (4)) having a continuous macropore structure with a total pore volume of, for example, more than 16 mL / g and 30 mL / g or less. In step II, for example, a mixture containing an aromatic vinyl monomer, a crosslinking agent in the range of, for example, 0.3 to 5 mol % in a total oil-soluble monomer having at least two or more vinyl groups in one molecule, an organic solvent in which the aromatic vinyl monomer and the crosslinking agent are dissolved but the polymer produced by polymerization of the aromatic vinyl monomer is not dissolved, and a polymerization initiator is prepared. In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (4) obtained in step I to obtain a fourth monolith.

[0132] Step I in the fourth method for producing a monolith is the same as in the first method for producing a monolith ion exchanger.

[0133] The monolith intermediate (4) obtained in step I is, for example, an organic polymer material having a crosslinked structure, preferably an aromatic vinyl polymer. The crosslink density of this polymer material is, for example, in the range of 0.1 to 5 mol %, preferably 0.3 to 3 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material.

[0134] The type of polymer material of the monolith intermediate (4) is the same as the type of polymer material of the monolith intermediate (3) in the third method for producing a monolith.

[0135] The total pore volume per weight of the monolith intermediate (4) obtained in step I in a dry state is, for example, more than 16 mL / g and 30 mL / g or less, preferably more than 16 mL / g and 25 mL / g or less. As shown in Fig. 7, the monolith intermediate (4) has a skeleton that is nearly rod-shaped. When this is allowed to coexist in a polymerization system, a porous body with a cocontinuous structure can be formed using the structure of the monolith intermediate (4) as a mold.

[0136] The monolith intermediate (4) obtained in step I has an average diameter of openings (mesopores) which are overlapping portions of macropores, in the range of, for example, 5 to 100 μm in a dry state.

[0137] Step II in the fourth monolith manufacturing method is a step of preparing a mixture containing, for example, an aromatic vinyl monomer, a crosslinking agent in the range of, for example, 0.3 to 5 mol % of all oil-soluble monomers having at least two or more vinyl groups in one molecule, an organic solvent that dissolves the aromatic vinyl monomer and the crosslinking agent but does not dissolve the polymer produced by polymerization of the aromatic vinyl monomer, and a polymerization initiator. Note that the order of steps I and II may be any.

[0138] The aromatic vinyl monomer used in the II step is not particularly limited as long as it is an aromatic vinyl monomer that contains a polymerizable vinyl group in the molecule and is lipophilic and highly soluble in an organic solvent, but it is preferable to select a vinyl monomer that produces the same or similar polymer material as the monolith intermediate (4) that is coexisted in the polymerization system. Specific examples of these vinyl monomers include styrene, α-methylstyrene, vinyltoluene, vinylbenzyl chloride, vinylbiphenyl, vinylnaphthalene, etc. These monomers can be used alone or in combination of two or more. The aromatic vinyl monomers that are preferably used are styrene, vinylbenzyl chloride, etc.

[0139] The amount of the aromatic vinyl monomer used in step II is, for example, in the range of 5 to 50 times, and preferably in the range of 5 to 40 times, by weight, the amount of the monolith intermediate (4) that is allowed to coexist during polymerization.

[0140] The crosslinking agent used in the II step preferably contains at least two polymerizable vinyl groups in the molecule and is highly soluble in an organic solvent. Examples of the crosslinking agent include divinylbenzene, divinylnaphthalene, divinylbiphenyl, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, butanediol diacrylate, etc. These crosslinking agents can be used alone or in combination of two or more. The amount of the crosslinking agent used is, for example, in the range of 0.3 to 5 mol% relative to the total amount of the vinyl monomer and the crosslinking agent (total oil-soluble monomers), and is particularly in the range of 0.3 to 3 mol%. It is preferable to use the crosslinking agent in an amount that is approximately equal to the crosslink density of the monolith intermediate (4) that is coexistent during the vinyl monomer / crosslinking agent polymerization. If the amounts of the two are too far apart, the crosslink density distribution in the produced monolith will be biased, and when an ion exchange group is introduced, cracks may easily occur during the ion exchange group introduction reaction.

[0141] The organic solvent used in the II step is, for example, an organic solvent in which the aromatic vinyl monomer and the crosslinking agent dissolve but the polymer produced by polymerization of the aromatic vinyl monomer does not dissolve, in other words, it is a poor solvent for the polymer produced by polymerization of the aromatic vinyl monomer. For example, when the aromatic vinyl monomer is styrene, the organic solvent is alcohols such as methanol, butanol, octanol, etc.; chain (poly)ethers such as diethyl ether, polyethylene glycol, polypropylene glycol, etc.; chain saturated hydrocarbons such as hexane, heptane, octane, etc.; esters such as ethyl acetate, isopropyl acetate, ethyl propionate, etc. In addition, even if it is a good solvent for polystyrene such as dioxane, THF, or toluene, it can be used as an organic solvent when it is used together with the poor solvent and the amount used is small. The amount of these organic solvents used can be such that the concentration of the aromatic vinyl monomer is, for example, 30 to 80% by weight. If the amount of the organic solvent used deviates from the above range and the aromatic vinyl monomer concentration is less than 30% by weight, the polymerization rate may decrease or the monolith structure after polymerization may deviate from the range of the fourth monolith. On the other hand, if the aromatic vinyl monomer concentration exceeds 80% by weight, the polymerization may proceed too far.

[0142] The polymerization initiator used in step II in the fourth method for producing a monolith is the same as the polymerization initiator used in step II in the third method for producing a monolith.

[0143] Step III in the fourth monolith manufacturing method is, for example, a step in which the mixture obtained in step II is allowed to stand and polymerized in the presence of the monolith intermediate (4) obtained in step I, thereby converting the continuous macropore structure of the monolith intermediate (4) into a co-continuous structure, thereby obtaining a fourth monolith which is a co-continuous structure monolith.

[0144] In step III, for example, in a reaction vessel, the monolith intermediate (4) is placed in a state of being impregnated with the mixture (solution). As described above, the mixture obtained in step II and the monolith intermediate (4) may be mixed in such a ratio that the amount of the aromatic vinyl monomer added is, for example, in the range of 5 to 50 times, preferably in the range of 5 to 40 times, by weight, relative to the monolith intermediate (4). This makes it possible to obtain a fourth monolith having a bicontinuous structure in which pores of appropriate size are three-dimensionally continuous and a thick skeleton is three-dimensionally continuous. In the reaction vessel, the aromatic vinyl monomer and the crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate (4), and polymerization proceeds within the skeleton of the monolith intermediate (4).

[0145] The polymerization conditions in step III in the fourth monolith manufacturing method are the same as those in step III in the third monolith manufacturing method. The fourth monolith ion exchanger can be obtained by carrying out step IV to introduce an ion exchange group into the fourth monolith obtained in step III. The method for introducing an ion exchange group into the fourth monolith is the same as the method for introducing an ion exchange group into the first monolith.

[0146] (Fifth monolithic ion exchanger) The fifth monolith ion exchanger is a monolith ion exchanger which comprises a continuous skeleton phase and a continuous pore phase, the skeleton having a plurality of particles with diameters in the range of 4 to 40 μm adhered to the surface or a plurality of protrusions with sizes in the range of 4 to 40 μm formed on the skeleton surface of the organic porous material, the average diameter of the continuous pores being in the range of 10 to 200 μm, the total pore volume being in the range of 0.5 to 10 mL / g, the ion exchange capacity per weight in a dry state being in the range of 1 to 9 mg equivalent / g, and the ion exchange groups being distributed in the organic porous ion exchanger.

[0147] The fifth monolith ion exchanger is a composite structure having an organic porous body having a continuous skeleton phase and a continuous pore phase, and further having a plurality of particles or a plurality of protrusions, and is a composite structure having a large number of particles or a large number of protrusions. The fifth monolith ion exchanger and a method for producing the same are disclosed in JP 2009-108294 A.

[0148] The plurality of particulate bodies are fixed to the skeletal surface of the organic porous body, and have a diameter in the range of, for example, 4 to 40 μm. The plurality of protrusions are formed on the skeletal surface of the organic porous body, and have a size in the range of, for example, 4 to 40 μm in a dry state. The diameter of the particulate bodies or the size of the protrusions is preferably in the range of 4 to 30 μm, and more preferably in the range of 4 to 20 μm. In this specification, the "particulate bodies" and "protrusions" are collectively referred to as "particulate bodies, etc."

[0149] The average diameter of the interconnected pores in a dry state is preferably in the range of 10 to 200 μm.

[0150] The continuous skeletal phase and the continuous pore phase of the fifth monolith ion exchanger are observed by SEM images. The basic structure of the fifth monolith ion exchanger includes a continuous macropore structure and a co-continuous structure. The skeletal phase of the fifth monolith ion exchanger appears as a continuous columnar structure, a continuous concave wall structure, or a composite of these, and has a shape that is clearly different from a particulate or protruding shape.

[0151] The fifth monolith ion exchanger includes a 5-1 monolith ion exchanger or a 5-2 monolith ion exchanger. The 5-1 monolith ion exchanger is a continuous macropore structure in which bubble-like macropores overlap each other, and the overlapping portions become openings with an average diameter of, for example, 10 to 120 μm in a dry state. The 5-2 monolith ion exchanger is a bicontinuous structure consisting of a three-dimensionally continuous skeleton with a continuous skeleton thickness of, for example, 0.8 to 40 μm in a dry state, and three-dimensionally continuous pores with an average diameter of, for example, 8 to 80 μm in a dry state between the skeletons. The monoliths of the 5-1 and 5-2 monolith ion exchangers before the introduction of ion exchange groups are called the 5-1 and 5-2 monoliths. The aforementioned average diameter and the thickness of the continuous skeleton in a dry state are determined by the same measurement method as the fourth monolith ion exchanger.

[0152] As shown in (A) to (E) in FIG. 8, the protrusions protruding from the skeleton surface 21 are the protrusions 22a to 22e. As shown in (A), the protrusions 22a have a shape close to a granule. As shown in (B), the protrusions 22b are hemispherical. As shown in (C), the protrusions 22c have a shape like a bulge on the skeleton surface. As shown in (D), the length of the protrusions 22d in the planar direction of the skeleton surface 21 is longer than the length of the protrusions 22d in the direction perpendicular to the skeleton surface 21. As shown in (E), the protrusions 22e have a shape protruding in multiple directions. The size of the protrusions is the length of the part where the width of each protrusion is the largest in the SEM image. As shown in FIG. 9, in the fifth monolith ion exchanger, multiple protrusions are formed on the skeleton surface of the organic porous body.

[0153] In the fifth monolith ion exchanger, the proportion of particles in the range of 4 to 40 μm in the total particles in a dry state is, for example, 70% or more, preferably 80% or more. The proportion of the particles refers to the number ratio of particles of a specific size in the total number of particles in a dry state. The surface of the skeleton phase is covered by all particles, for example, 40% or more, preferably 50% or more. The coverage ratio of the surface of the skeleton layer by all particles refers to the area ratio on the SEM image when the surface is observed by SEM, that is, the area ratio when the surface is viewed in plan. If the size of the particles covering the wall surface or skeleton deviates from the above range, the effect of improving the contact efficiency between the fluid and the skeleton surface and inside of the skeleton of the monolith ion exchanger may be easily reduced.

[0154] The fifth monolith ion exchanger in a dry state is observed at least three times under SEM, and the diameter or size of all particles in the SEM image in the whole field of view is calculated to confirm whether particles having a diameter or size in the range of, for example, 4 to 40 μm are observed. If they are observed in the whole field of view, it is determined that particles having a diameter or size in the range of, for example, 4 to 40 μm in a dry state are formed on the skeleton surface of the fifth monolith ion exchanger. In addition, the diameter or size of all particles in the SEM image in the dry state is calculated for each field of view according to the above, and the proportion of particles having a dry state of, for example, 4 to 40 μm in each field of view is determined. If the proportion of particles having a dry state of, for example, 4 to 40 μm in the whole field of view is 70% or more, it is determined that the proportion of particles having a dry state of, for example, 4 to 40 μm in the whole field of view is 70% or more. In addition, the coverage rate of the surface of the skeletal layer by all particles, etc. in the SEM image is determined for each field of view in accordance with the above, and if the coverage rate of the surface of the skeletal layer by all particles, etc. in the entire field of view is 40% or more, it is determined that the coverage rate of the surface of the skeletal layer of the fifth monolith ion exchanger by all particles, etc. is 40% or more.

[0155] In the fifth monolith ion exchanger, if the coverage of the skeletal phase surface by the particulate matter or the like is less than 40%, the effect of improving the contact efficiency between the reaction solution and the inside and surface of the skeletal structure of the monolith ion exchanger may be easily reduced. As a method for measuring the coverage by the particulate matter or the like, an image analysis method using an SEM image of the fifth monolith ion exchanger may be mentioned.

[0156] The total pore volume per weight of the fifth monolith ion exchanger in a dry state is, for example, in the range of 0.5 to 10 mL / g, preferably in the range of 0.8 to 8 mL / g. If the total pore volume is less than 0.5 mL / g, when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, the pressure loss during the passage of the liquid may become large, and further, the amount of permeated fluid per unit cross-sectional area may become small, resulting in a decrease in processing capacity. If the total pore volume exceeds 10 mL / g, the mechanical strength decreases, and the monolith ion exchanger may be deformed when a platinum group metal ion-supported catalyst is packed in a column and a reaction liquid is passed through the column, particularly when the liquid is passed through at a high flow rate. Furthermore, the contact efficiency between the reaction liquid and the monolith ion exchanger may decrease.

[0157] In the fifth monolith ion exchanger, the crosslink density of the polymer material constituting the skeleton may be, for example, in the range of 0.3 to 10 mol %, preferably in the range of 0.3 to 5 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material. The organic polymer material constituting the skeleton of the fifth monolith ion exchanger is the same as that of the first monolith ion exchanger.

[0158] In the fifth monolith ion exchanger, the material constituting the skeletal phase of the organic porous material and the particulate matter formed on the surface of the skeletal phase may be made of the same material having a continuous structure of the same kind, or made of different materials having a continuous structure of different kinds, etc. Examples of materials having a continuous structure of different kinds of different kinds include materials having different types of vinyl monomers, and materials having the same types of vinyl monomers and crosslinking agents but different mixing ratios.

[0159] The fifth monolith ion exchanger has a thickness of, for example, 1 mm or more, and is distinguished from a membrane-like porous body. The thickness of the fifth monolith ion exchanger is preferably in the range of 3 to 1000 mm.

[0160] The ion exchange capacity per weight in a dry state is as described above. In addition, the fact that "the ion exchange groups are distributed in the organic porous ion exchanger" is as described above.

[0161] (Fifth method for producing monolithic ion exchanger) The fifth monolithic ion exchanger can be produced, for example, by the following method.

[0162] The fifth monolith can be obtained, for example, by preparing a water-in-oil emulsion and then carrying out the following steps I to III. In step I, for example, the water-in-oil emulsion can be polymerized to obtain a monolithic organic porous intermediate (hereinafter, monolith intermediate (5)) having a continuous macropore structure with a total pore volume in the range of, for example, 5 to 30 mL / g. In step II, for example, a mixture containing a vinyl monomer, a crosslinking agent having at least two or more vinyl groups in one molecule, an organic solvent that dissolves the vinyl monomer and the crosslinking agent but does not dissolve the polymer produced by polymerization of the vinyl monomer, and a polymerization initiator is prepared. In step III, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (5) obtained in step I to obtain a fifth monolith.

[0163] Step I in the fifth method for producing a monolith is similar to step I in the third method for producing a monolith.

[0164] In the I step, when forming the water-in-oil emulsion, a polymerization initiator may be used as necessary. The polymerization initiator is preferably a compound that generates radicals by heat or light irradiation. The polymerization initiator may be water-soluble or oil-soluble, and examples thereof include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyric acid dimethyl, 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), benzoyl peroxide, lauroyl peroxide, potassium persulfate, ammonium persulfate, hydrogen peroxide-ferrous chloride, sodium persulfate-acidic sodium sulfite, and the like.

[0165] The monolith intermediate (5) obtained in step I has a continuous macropore structure. When this is allowed to coexist in a polymerization system, particulate matter and the like is formed on the surface of the skeletal phase of the continuous macropore structure using the structure of the monolith intermediate (5) as a template, or particulate matter and the like is formed on the surface of the skeletal phase of the cocontinuous structure. The monolith intermediate (5) is an organic polymer material having a crosslinked structure. The crosslink density of the polymer material is, for example, in the range of 0.3 to 10 mol %, preferably 0.3 to 5 mol %, of crosslinked structural units relative to the total structural units constituting the polymer material.

[0166] The type of polymer material of the monolith intermediate (5) is the same as the type of polymer material of the monolith intermediate (3) in the third method for producing a monolith.

[0167] The total pore volume per weight of the monolith intermediate (5) in a dry state obtained in step I is, for example, in the range of 5 to 30 mL / g, and preferably in the range of 6 to 28 mL / g. In order to set the total pore volume of the monolith intermediate (5) in the above numerical range, the ratio (by weight) of monomer to water may be, for example, about 1:5 to 1:35.

[0168] In step I, if the ratio of monomer to water is about 1:5 to 1:20, the monolith intermediate (5) will have a continuous macropore structure with a total pore volume of, for example, 5 to 16 mL / g, and the monolith obtained through step III will be a monolith No. 5-1. On the other hand, if the ratio of monomer to water is about 1:20 to 1:35, the monolith intermediate (5) will have a continuous macropore structure with a total pore volume of, for example, more than 16 mL / g and 30 mL / g or less, and the monolith obtained through step III will be a monolith No. 5-2.

[0169] The monolith intermediate (5) obtained in step I in the fifth monolith production method has openings (mesopores) which are overlapping portions of macropores, with an average diameter in a dry state of, for example, 20 to 200 μm.

[0170] Step II in the fifth monolith production method is the same as step II in the third monolith production method. In step III in the fifth monolith production method, for example, the mixture obtained in step II is left to stand and polymerized in the presence of the monolith intermediate (5) obtained in step I to obtain the fifth monolith.

[0171] Here, as disclosed in JP-A-7-501140, etc., a particle-aggregation type monolithic organic porous material can be obtained by statically polymerizing a vinyl monomer and a crosslinking agent in a specific organic solvent in the absence of the monolith intermediate (5). On the other hand, when the monolith intermediate (5) having a continuous macropore structure is present in the above polymerization system, the structure of the composite monolith after polymerization changes dramatically, and a fifth monolith having the above-mentioned specific skeletal structure can be obtained, instead of a particle-aggregation structure.

[0172] In the III step in the method for producing the fifth monolith, the internal volume of the reaction vessel is not particularly limited as long as it is large enough to allow the monolith intermediate (5) to exist in the reaction vessel. When the monolith intermediate (5) is placed in the reaction vessel, either one in which a gap is formed around the monolith in a plan view or one in which the monolith intermediate (5) fits almost without any gaps in the reaction vessel may be used. Among these, one in which the fifth monolith after polymerization is hardly subjected to pressure from the inner wall of the vessel and fits almost without any gaps in the reaction vessel is efficient with almost no distortion of the fifth monolith and almost no waste of reaction raw materials, etc. Even if the internal volume of the reaction vessel is large and there is a gap around the fifth monolith after polymerization, the vinyl monomer and crosslinking agent are adsorbed and distributed to the monolith intermediate (5), so that particle aggregate structures are hardly generated in the gaps in the reaction vessel.

[0173] In this step III, for example, the monolith intermediate (5) is placed in a reaction vessel in a state of being impregnated with the mixture (solution). As described above, the mixture obtained in step II and the monolith intermediate (5) may be mixed in such a ratio that the amount of vinyl monomer added is, for example, in the range of 3 to 50 times, preferably in the range of 4 to 40 times, by weight, relative to the monolith intermediate (5). This makes it possible to obtain a fifth monolith, which is a composite monolith having a specific skeleton while having an appropriate opening diameter. In the reaction vessel, the vinyl monomer and crosslinking agent in the mixture are adsorbed and distributed to the skeleton of the stationary monolith intermediate (5), and polymerization proceeds within the skeleton of the monolith intermediate (5).

[0174] In step III in the fifth method for producing a monolith, the polymerization conditions are almost the same as those in step III in the third method for producing a monolith.

[0175] When producing the above-mentioned fifth monolith, if step II or III is carried out under conditions that satisfy at least one of the following conditions (1) to (5), a monolith having particles and the like formed on the skeleton surface can be produced. (1) The polymerization temperature in step III is at least 5° C. lower than the 10-hour half-life temperature of the polymerization initiator. (2) The mole percentage of the crosslinking agent used in step II is at least twice the mole percentage of the crosslinking agent used in step I. (3) The vinyl monomer used in step II has a structure different from that of the oil-soluble monomer used in step I. (4) The organic solvent used in step II is a polyether having a molecular weight of 200 or more. (5) The concentration of the vinyl monomer used in step II is 30% by weight or less in the mixture in step II.

[0176] Preferred structures of the fifth monolith thus obtained include a continuous macropore structure ("5-1 monolith") in which bubble-like macropores overlap each other and the overlapping portions form openings with an average diameter of, for example, 10 to 120 μm in a dry state, and a co-continuous structure ("5-2 monolith") consisting of a three-dimensionally continuous skeleton with a thickness of, for example, 0.8 to 40 μm in a dry state and three-dimensionally continuous pores between the skeletons with a diameter of, for example, 8 to 80 μm in a dry state. The method for introducing ion exchange groups into the fifth monolith is the same as the method for introducing ion exchange groups into the first monolith.

[0177] [Platinum group metal ion supported catalysts] The platinum group metal ion-supported catalyst according to the present embodiment is a catalyst in which at least one of platinum group metal ions and platinum group metal complex ions is supported on the ion exchanger. That is, in the platinum group metal ion-supported catalyst, the platinum group metal is supported on the ion exchanger in an ionic state. For example, the platinum group metal ion-supported catalyst is a catalyst in which platinum group metal ions or platinum group metal complex ions are supported by ionic or coordinate bonds to quaternary ammonium groups in the ion exchanger. The platinum group metal ion-supported catalyst according to the present embodiment is preferably a catalyst in which at least one of platinum group metal ions and platinum group metal complex ions is supported on the non-particulate organic porous ion exchanger, for example, any one of the first monolith ion exchanger to the fifth monolith ion exchanger.

[0178] The platinum group metals are ruthenium, rhodium, palladium, osmium, iridium, and platinum. The platinum group metal ions are ions of the platinum group metals, and the valence of the platinum group metal ions varies depending on the type of platinum group metal. These platinum group metal ions may be one type alone or a combination of two or more types of metals. Among these, platinum ions and palladium ions are preferred in terms of their high catalytic activity.

[0179] The platinum group metal complex ion is a complex ion of the platinum group metal, such as a palladium complex ion, a platinum complex ion, an iridium complex ion, etc. These platinum group metal complex ions may be one type alone or a combination of two or more types of metals. Among these, platinum complex ions and palladium complex ions are preferred in terms of their high catalytic activity.

[0180] Whether platinum group metal ions or platinum group metal complex ions are supported in the platinum group metal ion supported catalyst can be confirmed by observation with a transmission electron microscope (TEM).

[0181] The amount of platinum group metal ions or platinum group metal complex ions supported in the platinum group metal ion supported catalyst ((mass converted into platinum group metal atoms / mass of platinum group metal ion supported catalyst in a dry state)×100) is, for example, in atomic terms, in the range of 0.01 to 10.0 mass%, preferably in the range of 0.1 to 5.0 mass%. When the amount of platinum group metal ions or platinum group metal complex ions supported is within the above range, it easily functions as a catalyst for carbon-carbon bond forming reactions, and is inexpensive from the viewpoint of raw materials. The amount of platinum group metal atoms in the platinum group metal ion supported catalyst is quantified using an ICP emission spectrometer.

[0182] There is no particular limitation on the method for producing the platinum group metal ion-supported catalyst, and the platinum group metal ion-supported catalyst can be obtained by supporting at least one of platinum group metal ions and platinum group metal complex ions on an ion exchanger by a known method. For example, there is a method in which the above-mentioned monolith ion exchanger in a dry state is immersed in an organic solution of a platinum group metal compound at a predetermined temperature for a predetermined time, and the platinum group metal ions are adsorbed on the monolith ion exchanger by ion exchange, or a method in which the monolith ion exchanger is immersed in an aqueous solution of a platinum group metal complex compound such as a tetraamminepalladium complex at a predetermined temperature for a predetermined time, and the platinum group metal ions are adsorbed on the monolith ion exchanger by ion exchange. illusion Examples of the method include a method in which ions are adsorbed onto a monolithic ion exchanger by ion exchange.

[0183] The platinum group metal ions or platinum group metal complex ions may be supported on the monolith ion exchanger by either a batch system or a flow system, and there is no particular limitation.

[0184] The platinum group metal compound used in the method for producing a platinum group metal ion-supported catalyst may be either an organic salt or an inorganic salt, and examples thereof include halides, sulfates, nitrates, phosphates, organic acid salts, inorganic complex salts, etc. Specific examples of platinum group metal compounds include palladium chloride, palladium nitrate, palladium sulfate, palladium acetate, tetraamminepalladium chloride, tetraamminepalladium nitrate, platinum chloride, tetraammineplatinum chloride, tetraammineplatinum nitrate, chlorotriammineplatinum chloride, hexaammineplatinum chloride, hexaammineplatinum sulfate, chloropentaammineplatinum chloride, cis-tetrachlorodiammineplatinum chloride, trans-tetrachlorodiammineplatinum chloride, rhodium chloride, rhodium acetate, hexaamminerhodium chloride, hexaamminerhodium bromide, hexaamminerhodium sulfate, pentaammineaquarhodium chloride, pentaammineaquarhodium nitrate, cis-dichlorodiammineplatinum ... Examples of the compound include tetraamminerhodium chloride, trans-dichlorotetraamminerhodium chloride, ruthenium chloride, hexaammineruthenium chloride, hexaammineruthenium bromide, hexaammineruthenium iodide, chloropentaammineruthenium chloride, cis-dichlorotetraammineruthenium chloride, trans-dichlorotetraamminerhodium chloride, iridium(III) chloride, iridium(IV) chloride, hexaammineiridium chloride, hexaammineiridium nitrate, chloropentaammineiridium chloride, chloropentaammineiridium bromide, hexaammineosmium chloride, hexaammineosmium bromide, and hexaammineosmium iodide. The amount of these compounds used is, for example, 0.005 to 30% by weight in terms of metal relative to the monolith ion exchanger that is the carrier.

[0185] When supporting platinum group metal ions or platinum group metal complex ions, the platinum group metal compound is usually dissolved in a solvent before use. Examples of the solvent include water; alcohols such as methanol, ethanol, propanol, butanol, and benzyl alcohol; ketones such as acetone and methyl ethyl ketone; nitriles such as acetonitrile; amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone, and mixtures thereof. In order to increase the solubility of the platinum group metal compound in the solvent, an acid such as hydrochloric acid, sulfuric acid, and nitric acid, or a base such as sodium hydroxide and tetramethylammonium hydroxide may be added.

[0186] <Method of forming carbon-carbon bond> The carbon-carbon bond forming method according to the embodiment of the present invention is a carbon-carbon bond forming method which, for example, comprises reacting an aromatic halide with an organoboron compound, (2) reacting an aromatic halide with a compound having an alkynyl group at a terminal, or (3) reacting an aromatic halide with a compound having an alkenyl group in the presence of the platinum group metal ion-supported catalyst to form a carbon-carbon bond.

[0187] The first embodiment of the carbon-carbon bond forming method (hereinafter also referred to as carbon-carbon bond forming method (1)) is a reaction in which an aromatic halide and an organoboron compound are reacted and coupled in the presence of the platinum group metal ion supported catalyst to produce a carbon-carbon single bond.

[0188] The organoboron compound used in the carbon-carbon bond forming method (1) is R 4 -B(OH) 2 (R 4 is an organic group, and is not particularly limited as long as it is an organic group, but is, for example, a linear alkyl group, a branched alkyl group, a cyclic alkyl group, an aromatic carbocyclic group, an aromatic heterocyclic group, etc., and a methyl group, an ethyl group, a nitro group, an amino group, a methoxy group, an ethoxy group, a carboxyl group, an acetyl group, etc. may be introduced into these groups as long as the effects of this embodiment are not impaired.

[0189] The organoboron compound used in the carbon-carbon bond forming method (1) is, for example, an aromatic boron compound represented by the following general formula (I). Ar 1 -B(OH) 2 (I) (In the formula, Ar 1 is an aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms.

[0190] In formula (I), Ar 1 Examples of aromatic carbocyclic or heterocyclic groups in the above formula include phenyl, naphthyl, biphenyl, anthranyl, pyridyl, pyrimidyl, indolyl, benzimidazolyl, quinolyl, benzofuranyl, indanyl, indenyl, and dibenzofuranyl groups. The position at which boron is bonded to the aromatic carbocyclic or heterocyclic group is not particularly limited, and it can be bonded to any position. In addition, one or more substituents may be introduced into the aromatic carbocyclic or heterocyclic group. Examples of the substituent include hydrocarbon groups such as methyl, ethyl, propyl, butyl, hexyl, and benzyl groups; alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy groups; 9-fluorenylmethoxycarbonyl, butoxycarbonyl, benzyloxycarbonyl, and nitro groups.

[0191] The aromatic halide used in the carbon-carbon bond forming method (1) is, for example, an aromatic halide represented by the following general formula (II). Ar 2 -X (II) (In the formula, Ar 2 is an aromatic carbocyclic group or aromatic heterocyclic group having 6 to 18 carbon atoms, and X is a halogen atom.

[0192] In formula (II), Ar 2 Examples of aromatic carbocyclic or heterocyclic groups are Ar 1The halogen atom may be bonded to any position of the aromatic carbocyclic group or aromatic heterocyclic group without any particular limitation. The aromatic carbocyclic group or aromatic heterocyclic group may have one or more substituents introduced therein. Examples of the substituent include hydrocarbon groups such as methyl, ethyl, propyl, butyl, hexyl, and benzyl groups; alkoxy groups such as methoxy, ethoxy, propoxy, and butoxy groups; 9-fluorenylmethoxycarbonyl, butoxycarbonyl, benzyloxycarbonyl, nitro, carboxyl, and amino groups.

[0193] X is a halogen atom, specifically a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom.

[0194] The formation of a carbon-carbon bond by the carbon-carbon bond forming method (1) refers to the formation of a carbon-carbon bond between an organic group obtained by removing a boron-containing functional group from an organoboron compound and an aromatic residue obtained by removing a halogen from an aromatic halide. For example, when the organoboron compound is an aromatic boron compound represented by formula (I) and the aromatic halide is an aromatic halide represented by formula (II), the resulting coupling product is a compound represented by formula (III). Ar 1 -Ar 2 (III) (In the formula, Ar 1 and Ar 2 is the same as in formulas (I) and (II) above.)

[0195] The ratio of the aromatic boron compound and aromatic halide used in the carbon-carbon bond forming method (1) is not particularly limited, but is, for example, in a molar ratio of aromatic boron compound:aromatic halide=0.5 to 2:1, and they may be used in equimolar amounts.

[0196] The second embodiment of the carbon-carbon bond forming method (hereinafter also referred to as carbon-carbon bond forming method (2)) is a reaction in which an aromatic halide is reacted with a compound having an alkynyl group at a terminal in the presence of the platinum group metal ion supported catalyst to form a carbon-carbon single bond.

[0197] The aromatic halide used in the carbon-carbon bond forming method (2) is, for example, the aromatic halide represented by the above formula (II).

[0198] The compound having an alkynyl group at its terminal, which is used in the carbon-carbon bond forming method (2), is, for example, a compound represented by formula (IV). HC≡CR 5 (IV) (In the formula, R 5 is a hydrogen atom, an aromatic carbocyclic group having 6 to 18 carbon atoms which may have a substituent, an aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent, an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, an alkenyl group having 2 to 18 carbon atoms which may have a substituent, or an alkynyl group having 2 to 10 carbon atoms which may have a substituent.

[0199] In formula (IV), R 5 Examples of the optionally substituted aromatic carbocyclic group having 6 to 18 carbon atoms or the optionally substituted aromatic heterocyclic group having 6 to 18 carbon atoms include Ar 1 and Ar 2 is the same as:

[0200] In formula (IV), R 5 Examples of the optionally substituted aliphatic hydrocarbon group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a hexyl group, an octyl group, a dodecyl group, and an octadecyl group.

[0201] In formula (IV), R 5Examples of the optionally substituted alkenyl group having 2 to 18 carbon atoms include a vinyl group, an allyl group, a methallyl group, a propenyl group, a butenyl group, a hexenyl group, an octenyl group, a decenyl group, and an octadecenyl group.

[0202] In formula (IV), R 5 Examples of the alkynyl group having 2 to 10 carbon atoms, which may have a substituent, include an ethynyl group, a propynyl group, a hexynyl group, and an octenyl group.

[0203] Examples of the substituent that may be possessed by these aromatic carbocyclic groups, aromatic heterocyclic groups, aliphatic hydrocarbon groups, alkenyl groups and alkynyl groups include hydrocarbon groups such as a hydroxyl group and a phenyl group, and heteroatom-containing hydrocarbon groups such as a methoxy group and a trifluoromethoxy group.

[0204] In the carbon-carbon bond forming method (2), for example, an aromatic halide represented by formula (II) is reacted with a compound represented by formula (IV) in the presence of the platinum group metal ion supported catalyst to give a product represented by formula (V). Ar 2 -C≡CR 5 (V) (In the formula, Ar 2 and R 5 is the same as in formulas (II) and (IV).

[0205] The ratio of the aromatic halide to the compound having an alkynyl group at a terminal used in the carbon-carbon bond forming method (2) is not particularly limited, but is, for example, in the range of a molar ratio of aromatic halide:compound having an alkynyl group at a terminal of 0.5 to 3:1, and they may be used in equimolar amounts.

[0206] The third embodiment of the carbon-carbon bond forming method (hereinafter also referred to as carbon-carbon bond forming method (3)) is a reaction in which an aromatic halide is reacted with a compound having an alkenyl group in the presence of the platinum group metal ion supported catalyst to form a carbon-carbon single bond.

[0207] The aromatic halide used in the carbon-carbon bond forming method (3) is, for example, the aromatic halide represented by the above formula (II).

[0208] The compound having an alkenyl group used in the carbon-carbon bond forming method (3) is, for example, a compound represented by formula (VI). R 6 HC=CR 7 R 8 (VI) (In the formula, R 6 ,R 7 ,R 8 are each independently a hydrogen atom, an aromatic carbocyclic group having 6 to 18 carbon atoms which may have a substituent, an aromatic heterocyclic group having 6 to 18 carbon atoms which may have a substituent, an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, a carboxylic acid derivative, an acid amide derivative, or a cyano group.

[0209] In formula (VI), R 6 ,R 7 ,R 8 an aromatic carbocyclic group having 6 to 18 carbon atoms which may be substituted, an aromatic heterocyclic group having 6 to 18 carbon atoms which may be substituted, and Substituents Optional carbon number: 1 to 18 Fat Examples of the aliphatic hydrocarbon group include R 5 is the same as:

[0210] In formula (VI), R 6 ,R 7 ,R 8 Examples of the carboxylic acid derivative include alkoxycarbonyl groups such as methoxycarbonyl, ethoxycarbonyl, butoxycarbonyl, etc.

[0211] In formula (VI), R 6 ,R 7 ,R 8 Examples of the acid amide derivative include carbamoyl groups such as N-methylcarbamoyl group and N,N-dimethylcarbamoyl group.

[0212] In the carbon-carbon bond forming method (3), an aromatic halide represented by formula (II) is reacted with a compound represented by formula (VI) in the presence of the platinum group metal ion supported catalyst to obtain a product represented by formula (VII). R 6 Ar 2 C=CR 7 R 8 (VII) (In the formula, Ar 2 ,R 6 ,R 7 ,R 8 is the same as the above formula (II) and formula (VI).

[0213] The ratio of the aromatic halide to the compound having an alkenyl group used in the carbon-carbon bond forming method (3) is not particularly limited, but is, for example, in the range of a molar ratio of aromatic halide:compound having an alkenyl group=0.5 to 2:1, and they may be used in equimolar amounts.

[0214] In the carbon-carbon bond forming reactions (1) to (3), the amount of the platinum group metal ion supported catalyst used is, for example, in the range of 0.01 to 20 mol % in terms of platinum group metal relative to the aromatic halide.

[0215] In the carbon-carbon bond forming method, the coupling reaction may be carried out using a solvent or without a solvent. Examples of the solvent used include water, an organic solvent, and a mixture thereof. Examples of the organic solvent include alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, and glycerin; and cyclic ethers such as tetrahydrofuran and dioxane.

[0216] The atmosphere in which the carbon-carbon bond forming method is carried out may be air, but is preferably an inert gas atmosphere such as nitrogen, argon, etc. The reaction temperature is not particularly limited, but is set arbitrarily within the range of, for example, -20°C to 150°C, and the reaction time is not particularly limited, but is set within the range of, for example, 1 minute to 24 hours.

[0217] In the carbon-carbon bond forming reaction, it is preferable to use a base, and more preferable to use an inorganic base. Examples of the base to be used include inorganic bases such as sodium carbonate, sodium hydrogen carbonate, potassium carbonate, cesium carbonate, potassium acetate, sodium phosphate, potassium phosphate, and barium hydroxide; and organic bases such as potassium phenolate, sodium methoxide, sodium ethoxide, potassium butoxide, trimethylamine, and triethylamine. The amount of these bases to be used is set, for example, in the range of 50 to 300 mol% relative to the aromatic halide.

[0218] In the carbon-carbon bond forming method according to this embodiment, the reaction for producing the carbon-carbon bond may be carried out by passing a raw material liquid for the reaction through a platinum group metal catalyst.

[0219] In the carbon-carbon bond forming method according to the present embodiment, it is preferable to carry out the carbon-carbon bond forming reactions (1) to (3) by, for example, introducing a raw material liquid (i) containing the aromatic halide and the organoboron compound, a raw material liquid (ii) containing the aromatic halide and the compound having an alkynyl group at the terminal, or a raw material liquid (iii) containing the aromatic halide and the compound having an alkenyl group into a filled container filled with a platinum group metal ion supported catalyst through an inlet path of the filled container, passing the raw material liquid through the platinum group metal ion supported catalyst, and discharging the reaction liquid from a discharge path of the filled container, thereby forming a carbon-carbon bond.

[0220] In the carbon-carbon bond forming method, for example, raw material liquid (i), raw material liquid (ii), or raw material liquid (iii) is an inorganic base-dissolved raw material liquid in which a raw material and an inorganic base are dissolved in water or a hydrophilic solvent, and the inorganic base-dissolved raw material liquid may be introduced into a packed container filled with a platinum group metal ion-supported catalyst through an inlet path of the packed container, the inorganic base-dissolved raw material liquid is passed through the platinum group metal ion-supported catalyst, and the reaction liquid is discharged from a discharge path of the packed container to carry out the carbon-carbon bond forming reaction.

[0221] Furthermore, in the carbon-carbon bond forming method, for example, the raw material liquid (i), raw material liquid (ii), or raw material liquid (iii) may be a hydrophobic solvent raw material liquid in which a raw material is dissolved in a hydrophobic organic solvent, and a mixture of the hydrophobic solvent raw material liquid and an inorganic base aqueous solution in which an inorganic base is dissolved may be introduced into a filled container through an inlet path of the filled container filled with a platinum group metal ion supported catalyst, the hydrophobic solvent raw material liquid and the inorganic base aqueous solution may be passed through the platinum group metal ion supported catalyst, and the reaction liquid may be discharged from a discharge path of the filled container to carry out the carbon-carbon bond forming reaction.

[0222] The carbon-carbon bond forming method according to the present embodiment can form a carbon-carbon bond to obtain a desired compound, and can obtain the target product in high yield. In particular, the carbon-carbon bond forming reaction can be performed in high yield even with aromatic bromides. In addition, the reaction time is short and the target product can be obtained in high yield. According to the carbon-carbon bond forming method according to the present embodiment, the carbon-carbon bond forming method for forming a carbon-carbon bond to obtain a desired compound can be performed in a fixed-bed continuous flow system, and the carbon-carbon bond reaction can be performed in high yield with various raw materials. In addition, from the viewpoint of production efficiency, a high-concentration raw material solution can be used. EXAMPLES

[0223] EXAMPLES The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0224] <Example 1> According to the fifth method for producing a monolithic ion exchanger, a monolith was produced, and an ion exchange group was introduced into the obtained monolith.

[0225] (Manufacturing of Monolith Intermediate (Process I)) 9.28g of styrene as a monomer, 0.19g of divinylbenzene, 0.50g of sorbitan monooleate (hereinafter abbreviated as SMO) as a surfactant, and 0.25g of 2,2'-azobis(isobutyronitrile) as a polymerization initiator were mixed and dissolved uniformly. Next, this styrene / divinylbenzene / SMO / 2,2'-azobis(isobutyronitrile) mixture was added to 180g of pure water and stirred under reduced pressure using a planetary stirring device, a vacuum stirring and degassing mixer (manufactured by EME Co., Ltd.) to obtain a water-in-oil type emulsion. This emulsion was quickly transferred to a reaction vessel, sealed, and polymerized at 60°C for 24 hours under static conditions. After the polymerization was completed, the contents were removed, extracted with methanol, and then dried under reduced pressure to produce a monolith intermediate having a continuous macropore structure. The internal structure of the monolith intermediate (dried body) obtained in this manner was observed by SEM. An SEM image is shown in Figure 10. Although the wall separating two adjacent macropores is extremely thin and rod-like, it has a continuous macropore structure. The average diameter of the openings (mesopores) where the macropores overlap, as measured by mercury intrusion porosimetry, was 40 μm, and the total pore volume was 18.2 mL / g.

[0226] (Monolith Manufacturing (II Process)) Next, 216.6 g of styrene as a monomer, 4.4 g of divinylbenzene as a crosslinking agent, 220 g of 1-decanol as an organic solvent, and 0.8 g of 2,2'-azobis(2,4-dimethylvaleronitrile) as a polymerization initiator were mixed and dissolved uniformly (II step).

[0227] (Manufacturing of Monoliths (III Process)) Next, the monolith intermediate was placed in a reaction vessel, immersed in the styrene / divinylbenzene / 1-decanol / 2,2'-azobis(2,4-dimethylvaleronitrile) mixture, and degassed in a vacuum chamber. The reaction vessel was then sealed and allowed to polymerize for 24 hours at 50°C under static conditions. After polymerization was completed, the contents were removed, extracted with acetone using a Soxhlet extractor, and then dried under reduced pressure (III step).

[0228] The internal structure of the monolith (dried body) containing 1.2 mol% of a crosslinking component made of a styrene / divinylbenzene copolymer thus obtained was observed by SEM, and the results are shown in FIG. 11. As is clear from FIG. 11, the skeleton and pores of this monolith were three-dimensionally continuous, consisting of a continuous skeleton phase and a continuous pore phase, respectively, and the two phases were intertwined to form a co-continuous structure. The thickness of the continuous skeleton measured from the SEM image was 20 μm. The average diameter of the three-dimensionally continuous pores of this monolith, measured by mercury intrusion porosimetry, was 70 μm, and the total pore volume was 4.4 mL / g. The average diameter of the pores was determined from the maximum value of the pore distribution curve obtained by mercury intrusion porosimetry.

[0229] (Production of chloromethylated monoliths) The produced monolith was placed in a columnar reactor, and a solution containing 1600 g of chlorosulfonic acid, 400 g of tin tetrachloride, and 2500 mL of dimethoxymethane was circulated and passed through the monolith, which was reacted at 30° C. for 5 hours to introduce chloromethyl groups. After the reaction was completed, the chloromethylated monolith was washed with a mixed solvent of THF / water = 2 / 1 (vol), and then further washed with THF to obtain a chloromethylated monolith.

[0230] (Production of monolithic ion exchanger) 390 mL of THF and 30 mL of N,N-dimethylbenzylamine as a tertiary amine were added to 20 g of the chloromethylated monolith, and the mixture was reacted for 6 hours at 60° C. After the reaction was completed, the product was washed with methanol and then with pure water to obtain a monolith ion exchanger composed of a polymer chain represented by the following formula (4). [ka] (In the formula, Polymer represents a styrene-divinylbenzene copolymer.)

[0231] The anion exchange capacity of the obtained monolith ion exchanger in the dry state was 2.9 mg equivalent / g, and it was confirmed that quaternary ammonium groups were quantitatively introduced. As is clear from Figure 11, the monolith cation exchanger had a bicontinuous structure in which the framework and pores were three-dimensionally continuous and the two phases were entangled. In addition, the thickness of the framework in the dry state measured from SEM images was 20 μm, and the average diameter of the three-dimensionally continuous pores of this monolith anion exchanger in the dry state was 70 μm, and the total pore volume in the dry state was 4.4 mL / g, as determined by mercury intrusion porosimetry.

[0232] (Production of platinum group metal ion supported catalysts) The produced monolith ion exchanger was dried under reduced pressure. The weight of the monolith ion exchanger after drying was 8.7 g. This dried monolith ion exchanger was immersed in dilute hydrochloric acid in which 146 mg of palladium chloride was dissolved at 25° C. for 24 hours to support tetrachloropalladium acid ions. After completion of the immersion, it was washed several times with pure water to prepare a Pd ion-supported monolith ion exchanger. The amount of palladium supported in the obtained Pd ion-supported monolith ion exchanger was determined by an ICP emission spectrometer (manufactured by Hitachi High-Tech Science, PS3520UVDDII type), and the amount of palladium supported was 1.0 wt%.

[0233] Hereinafter, the platinum group metal ion-supported catalyst obtained in Example 1 will be referred to as "Pd ion-supported monolith ion exchanger."

[0234] <Example 2> (Carbon-carbon bond formation reaction using Pd ion-supported monolithic ion exchanger) [ka] A 4-methyltetrahydropyran (4-MTHP) / ethanol (32mL, 1:1 (vol)) solution of 2-bromobenzonitrile (5.82g, 32.0mmol) as an aromatic halide and 4-methylphenylboronic acid (4.78g, 35.2mmol) as an organic boron compound was added to a solution of sodium hydroxide (35.2mmol) in water (22mL) as an inorganic base and stirred. This solution was passed through a SUS column filled with Pd ion-supported monolith ion exchanger (φ4.6×30mm) and heated to 80℃ at a flow rate of 0.3mL / min, and collected in a flask containing a saturated aqueous ammonium chloride solution. The organic layer of the obtained liquid was analyzed by GC (Shimadzu Corporation, GC-2010 type) and found to have a conversion rate of 80% to have 2-cyano-4'-methylbiphenyl.

[0235] <Example 3> [ka] A solution of 4-bromobenzotrifluoride (10.8 g, 48.0 mmol) as an aromatic halide and phenylboronic acid (6.44 g, 52.8 mmol) as an organic boron compound in 4-MTHP / ethanol (48 mL, 1:1 (vol)) was added to a solution of sodium hydroxide (52.8 mmol) as an inorganic base in water (33 mL) and stirred. This solution was passed through a SUS column filled with Pd ion-supported monolithic ion exchanger (φ4.6 × 30 mm) and heated to 80 ° C. at a flow rate of 0.3 mL / min, and collected in a flask containing a saturated ammonium chloride aqueous solution. The organic layer of the obtained liquid was analyzed by GC, and 4-(trifluoromethyl)biphenyl was obtained with a conversion rate of 71%.

[0236] <Example 4> [ka] A solution of 2-bromonitrobenzene (6.46 g, 32.0 mmol) as an aromatic halide and phenylboronic acid (4.29 g, 35.2 mmol) as an organic boron compound in 4-MTHP / ethanol (32 mL, 1:1 (vol)) was added to a solution of sodium hydroxide (35.2 mmol) as an inorganic base in water (22 mL) and stirred. This solution was passed through a SUS column filled with Pd ion-supported monolithic ion exchanger (φ4.6 × 30 mm) and heated to 80 ° C. at a flow rate of 0.3 mL / min, and collected in a flask containing a saturated ammonium chloride aqueous solution. The organic layer of the obtained liquid was analyzed by GC, and 2-nitrobiphenyl was obtained with a conversion rate of 81%.

[0237] <Comparative Example 1> 25.1 g of the chloromethyl monolith obtained in Example 1 was added with 400 mL of THF and 56 mL of a 30% aqueous solution of trimethylamine as a tertiary amine, and reacted for 3 hours at 40° C. After completion of the reaction, the product was washed with methanol and then with pure water to obtain a monolith strong base anion exchanger composed of a polymer chain represented by the following formula (5). [ka] (In the formula, Polymer represents a styrene-divinylbenzene copolymer.)

[0238] The anion exchange capacity of the obtained monolith anion exchanger was 4.6 mg equivalent / g in the dry state, confirming that quaternary ammonium groups were quantitatively introduced. In addition, the thickness of the skeleton in the dry state measured from SEM images was 20 μm, and the average diameter of the three-dimensionally connected pores in the dry state of the monolith anion exchanger determined by mercury intrusion porosimetry was 70 μm, and the total pore volume in the dry state was 4.4 mL / g.

[0239] The monolith strong base anion exchanger obtained was dried under reduced pressure. The weight of the monolith strong base anion exchanger after drying was 18.0 g. This dried monolith was immersed in dilute hydrochloric acid in which 1.80 g of palladium chloride was dissolved at 25° C. for 24 hours to support tetrachloropalladium acid ions. After completion of the immersion, it was washed several times with pure water to prepare a monolith ion exchanger supporting Pd ions. The amount of palladium supported in the obtained monolith ion exchanger supporting Pd ions was determined by ICP emission spectrometry, and the amount of palladium supported was 4.8 wt%.

[0240] Hereinafter, the platinum group metal ion-supported catalyst obtained in Comparative Example 1 will be referred to as "Pd ion-supported monolith strong base anion exchanger."

[0241] <Comparative Example 2> [ka]

[0242] A toluene (2.0 mL) solution of 4-bromoacetophenone (0.796 g, 4.0 mmol) as an aromatic halide was fed at 0.1 mL / min, and a water (4.0 mL) solution of phenylboronic acid (0.536 g, 4.4 mmol) as an organic boron compound and sodium hydroxide (4.4 mmol) as an inorganic base was fed at 0.2 mL / min, and the respective solutions were combined at a joint. The combined liquid was passed through a SUS column filled with the Pd ion-supported monolithic strong base anion exchanger (φ4.6×30 mm) produced in Comparative Example 1 and heated to 80° C., and collected in a flask containing a saturated aqueous ammonium chloride solution. The organic layer of the obtained liquid was analyzed by GC, and 4-acetylbiphenyl was obtained with a conversion rate of 33%.

[0243] <Comparative Example 3> The procedure was carried out in the same manner as in Example 2, except that the Pd ion-supporting monolithic ion exchanger was changed to a Pd ion-supporting monolithic strong basic anion exchanger, and as a result, 2-cyano-4'-methylbiphenyl was obtained with a conversion rate of 14%.

[0244] In this way, by using the platinum group metal ion supported catalyst of the examples, a carbon-carbon bond forming reaction could be carried out in high yield even with aromatic bromides. [Explanation of symbols]

[0245] 1 skeletal phase, 2 pore phase, 10 bicontinuous structure, 11 rectangular image area, 12 skeletal part, 13 macropore, 21 skeletal surface, 22a, 22b, 22c, 22d, 22e protrusions.

Claims

1. A platinum group metal ion supported catalyst for carbon-carbon bond forming reactions, comprising: General formula (1) 【Chemistry 1】 (In the formula R 1 represents an alkyl group having 6 to 20 carbon atoms; or a benzyl group which may be substituted with an alkyl group having 1 to 4 carbon atoms; R 2 , R 3 each independently represents an alkyl group having 1 to 4 carbon atoms, L represents a linker moiety, and Polymer represents a polymer chain.

1. A platinum group metal ion supported catalyst, comprising an ion exchanger comprising a polymer chain represented by the formula:

2. 2. The platinum group metal ion supported catalyst of claim 1, The ion exchanger is a non-particulate organic porous ion exchanger comprising a continuous framework phase and a continuous pore phase, the thickness of the continuous framework being in the range of 1 to 100 μm, the average diameter of the continuous pores being in the range of 1 to 1000 μm, the total pore volume being in the range of 0.5 to 50 mL / g, and the ion exchange capacity per weight in a dry state being in the range of 1 to 9 mg equivalent / g, and ion exchange groups being distributed throughout the ion exchanger.

3. The platinum group metal ion supported catalyst according to claim 1 or 2, A platinum group metal ion supported catalyst, characterized in that the amount of at least one of the platinum group metal ions and platinum group metal complex ions supported is in the range of 0.01 to 10.0 mass % in terms of platinum group metal atoms.

4. The platinum group metal ion supported catalyst according to any one of claims 1 to 3, R in general formula (1) 1 is a dodecyl group or a benzyl group.

5. The platinum group metal ion supported catalyst according to any one of claims 1 to 4, R in general formula (1) 2 , R 3 and each independently represent a methyl group or an ethyl group.

6. The platinum group metal ion supported catalyst according to any one of claims 1 to 5, A platinum group metal ion supported catalyst, characterized in that L in general formula (1) is a methylene group.

7. The platinum group metal ion supported catalyst according to any one of claims 1 to 6, A platinum group metal ion supported catalyst, wherein the polymer chain of the ion exchanger is a styrene-divinylbenzene copolymer.

8. A method for forming a carbon-carbon bond, comprising: (1) reacting an aromatic halide with an organoboron compound; (2) reacting an aromatic halide with a compound having an alkynyl group at a terminal; or (3) reacting an aromatic halide with a compound having an alkenyl group to form a carbon-carbon bond, a raw material liquid (i) containing the aromatic halide and the organoboron compound, a raw material liquid (ii) containing the aromatic halide and the compound having an alkynyl group at its terminal, or a raw material liquid (iii) containing the aromatic halide and the compound having an alkenyl group is introduced into a filled container filled with a platinum group metal ion supported catalyst through an inlet path of the filled container, the raw material liquid is passed through the platinum group metal ion supported catalyst, and a reaction liquid is discharged from a discharge path of the filled container, thereby carrying out a carbon-carbon bond forming reaction; A method for forming a carbon-carbon bond, wherein the platinum group metal ion supported catalyst is the platinum group metal ion supported catalyst according to any one of claims 1 to 7.

9. The carbon-carbon bond forming method according to claim 8, The carbon-carbon bond forming method comprises carrying out the carbon-carbon bond forming reaction in the presence of an inorganic base.

10. The carbon-carbon bond forming method according to claim 8 or 9, The raw material liquid (i), the raw material liquid (ii), or the raw material liquid (iii) is an inorganic base-dissolved raw material liquid in which a raw material and an inorganic base are dissolved in water or a hydrophilic solvent, a supply path of the inorganic base-dissolved raw material solution through the platinum group metal ion-supported catalyst, and a reaction solution is discharged from a discharge path of the container, thereby carrying out a carbon-carbon bond-forming reaction.

11. The carbon-carbon bond forming method according to claim 8 or 9, the raw material liquid (i), the raw material liquid (ii), or the raw material liquid (iii) is a hydrophobic solvent raw material liquid in which a raw material is dissolved in a hydrophobic organic solvent; a mixture of the hydrophobic solvent stock solution and an aqueous inorganic base solution in which an inorganic base is dissolved is introduced into a filled container through an inlet path of the filled container in which the platinum group metal ion supported catalyst is filled, the hydrophobic solvent stock solution and the aqueous inorganic base solution are passed through the platinum group metal ion supported catalyst, and a reaction solution is discharged from a discharge path of the filled container, thereby carrying out a carbon-carbon bond forming reaction.

Citation Information

Patent Citations

  • Plate for construction

    JP1977055215A

  • Semiconductor device

    JP1981038862A

  • Agent for suppressing cholesterol level

    JP1989316324A

  • Transition metal-immobilized reactor and its manufacturing method

    JP2008212765A

  • Carbon-carbon bond-forming method and platinum group metal carrier catalyst for carbon-carbon bond-forming reaction

    JP2014015420A